Alternative fiber and microfibrillated cellulose coated wrapping paper and films and substrates

By using packaging materials prepared from agricultural-based microfibrillated cellulose (A-MFC) and other additives, the problem of existing food packaging materials being difficult to meet the sustainability and functional requirements has been solved, and an efficient, environmentally friendly and Performance improvements.

CN119343499APending Publication Date: 2025-01-21WM WRIGLEY JR CO +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380039245.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-12
Filing Date
2023-05-12
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing food packaging materials mainly rely on non-biodegradable and non-renewable materials, such as plastics, which lead to environmental pollution and waste of resources, and are difficult to meet the sustainability and functional requirements.

Method used

Using non-wood biopolymer fibers, specifically agro-based microfibrillated cellulose (A-MFC), they are prepared by incorporating them into films or coatings in combination with other additives such as chitosan, cationic starch and glycerol. Packaging materials with enhanced tensile strength and barrier properties.

Benefits of technology

It achieves the biodegradability and sustainability of packaging materials, while improving its mechanical properties and barrier capabilities, meeting the dual needs of food packaging for functionality and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343499A_ABST
    Figure CN119343499A_ABST
Patent Text Reader

Abstract

Sustainable paper-based packaging materials, such as packaging materials comprising agrobased microfibrillated cellulose (A-MFC), are described. The packaging material includes coatings and films prepared from A-MFCs derived from hemp stalk cores, cocoa pod shells and other agricultural residues or byproducts and having high levels of primary and / or secondary fine fibers. The method of making the A-MFC may involve a reduced amount of energy compared to wood-derived materials, and the packaging material may have enhanced barrier and mechanical properties, such as enhanced oil and grease resistance.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of and priority to U.S. Provisional Patent Application Serial No. 63 / 364,613, filed on May 12, 2022, the disclosure of which is incorporated herein by reference in its entirety. Technical Field

[0003] The presently disclosed subject matter relates to non-wood biopolymer fibers, such as agro-based microfibrillated cellulose (A-MFC), and their use in packaging materials, such as for food and / or beverage packaging. The non-wood biopolymer fibers may include fibers derived from non-wood lignocellulosic raw materials (including agricultural residues and industrial lignocellulosic waste), and / or fibers having high levels of primary and / or secondary fines and having been microfibrillated and optionally chemically modified. The fibers may be incorporated into films or coatings or composite layers to obtain packaging materials having enhanced tensile strength and elongation while also having a barrier to oil, grease, water, water vapor, air, and oxygen.

[0004] abbreviation

[0005] % = Percent

[0006] ℃ = degrees Celsius

[0007] μeq = micro equivalent

[0008] μm = micrometer

[0009] AGU = Anhydroglucose

[0010] AH = Autohydrolysis

[0011] AKD = Alkyl Ketene Dimer

[0012] A-MFC = Agro-based microfibrillated cellulose

[0013] CFS = Cocoa Nut Shell

[0014] CH or Chi = Chitosan

[0015] cm = centimeters

[0016] CM = Carboxymethyl

[0017] CM2 = Enhanced Chemical Carboxymethylation

[0018] CMA = Sodium Chloroacetate

[0019] CMC = Carboxymethyl Cellulose

[0020] CMPI = carboxymethylation followed by periodate oxidation (or MFC from fibers that were both carboxymethylated and periodate oxidized)

[0021] CM-PI = a mixture of carboxymethylated MFC and periodate-oxidized MFC

[0022] CNC = Cellulose Nanocrystals

[0023] CPH = Cocoa Pod Husk

[0024] CPS or cP = Centipoise

[0025] CS or St or ST = Cationic starch

[0026] DAC = Dialdehyde Cellulose

[0027] DP = Degree of Polymerization

[0028] DS = Degree of Substitution

[0029] FTIR = Fourier Transform Infrared

[0030] g = grams

[0031] GL or GLY or Gly = Glycerol

[0032] GS = Gurley seconds

[0033] gsm = grams per square meter

[0034] HH = Hemp stalk core

[0035] HM = Cannabis Mixture

[0036] HW = Hardwood

[0037] KWH / T = kilowatt-hour / ton

[0038] l = liter

[0039] MFC = Microfibrillated Cellulose

[0040] min = minutes

[0041] ml = milliliters

[0042] mm = millimeters

[0043] OGR = Oil and Grease Resistant

[0044] PI = Periodate oxidation

[0045] rpm = revolutions per minute

[0046] RT = Room temperature

[0047] SAP = Superabsorbent polymer

[0048] SEM = Scanning Electron Microscope

[0049] TEM = Transmission Electron Microscope

[0050] UCPH = Unbleached Cocoa Pod Husk

[0051] WVTR = Water Vapor Transmission Rate Background Art

[0052] Food packaging plays an important role in daily life and the current economy. Food packaging can help enhance the value of food, reduce food waste, and reduce food spoilage by maintaining food quality during storage, transportation, and distribution, as well as through other useful features (Gutta et al., 2013).

[0053] According to a recent study, the global packaging market will exceed $1 trillion by 2021 (Smithers, 2018). However, the growth of the packaging market has also raised concerns about environmental sustainability. Every year, a large amount of packaging materials are used with the intention of "use and throw", and most of these materials are also made of non-biodegradable and non-renewable materials such as plastics, glass and metals. Plastic polymers used in food packaging may have adverse effects on both human health and the environment. These disposable and short-term use plastic polymers can be discarded as solid waste, which may eventually enter landfills and may eventually end up in soil and marine waterways (MacArthur et al., 2016) (Jambeck et al., 2015).

[0054] Consumer demand for sustainability and recent changes in government policies and regulations, such as initiatives to ban or reduce the use of plastics (especially single-use plastics), have prompted companies to consider alternative solutions. In addition, consumers' increasing preference for convenience, small package sizes, and minimally processed, fresh, and healthy foods has led to the need for highly functional and sustainable food packaging (Tyagi et al., 2022). Therefore, there is a focus on sustainable and / or biodegradable packaging in many markets, including the food and beverage industry, to overcome challenges in functionality, environmental management, and cost while maintaining acceptable biodegradability characteristics.

[0055] Therefore, there is a continuing need for new sustainable food packaging materials and methods of preparing food packaging materials from sustainably sourced materials, including biomass materials that are currently considered low-value by-products and / or waste. Summary of the invention

[0056] The presently disclosed subject matter will now be described more fully hereinafter, in which some but not all embodiments of the presently disclosed subject matter are described. Indeed, the presently disclosed subject matter may be embodied in many different forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided so that this disclosure will satisfy applicable legal requirements.

[0057] In some embodiments, the presently disclosed subject matter provides a packaging material comprising a film or coating comprising agro-based microfibrillated cellulose (A-MFC), wherein the A-MFC comprises microfibrillated cellulose (MFC) prepared from pulp from a non-wood lignocellulosic feedstock, wherein the film or coating has a viscosity less than about 5 percent (%) and / or less than about 2.5 grams / square meter (g / m 2 ) of the invention, wherein the hot oil has a temperature of about 65 degrees Celsius (°C).

[0058] In some embodiments, the non-wood lignocellulosic feedstock comprises one or more agricultural residues and / or industrial byproducts. In some embodiments, the non-wood lignocellulosic feedstock is selected from the group consisting of hemp stalk cores, a mixture of hemp stalk cores and hemp bast, bagasse, cocoa pod shells, and combinations thereof.

[0059] In some embodiments, the A-MFC comprises modified A-MFC, wherein the modified A-MFC comprises MFC derived from chemically modified pulp. In some embodiments, the modified A-MFC comprises carboxymethylated A-MFC; oxidized A-MFC; carboxymethylated and oxidized MFC; or a combination thereof. In some embodiments, the oxidized A-MFC comprises dialdehyde cellulose.

[0060] In some embodiments, the film or coating comprises about 5 weight percent (wt%) to about 90 wt% A-MFC, optionally wherein the film or coating comprises about 40 wt% A-MFC to about 80 wt% A-MFC. In some embodiments, the film or coating further comprises one or more of chitosan, cationic starch, glycerol, triethyl citrate, polyhydroxyalkanoate (PHA), and alkyl ketene dimer (AKD).

[0061] In some embodiments, the A-MFC has a total fines level of about 50% to about 95%. In some embodiments, the A-MFC has an average fiber length of about 0.1 mm to about 0.45 mm.

[0062] In some embodiments, the film or coating has a thickness of about 1 micron to about 200 microns, optionally wherein the film or coating is a coating having a thickness of about 1 micron to about 30 microns or a film having a thickness of about 10 microns to about 200 microns, and optionally wherein the film has a thickness of about 20 microns to about 140 microns. In some embodiments, the film or coating has a thickness of about 0.5 cubic centimeters per gram (cm 3 / g) to about 2.0cm 3 / g of bulk volume.

[0063] In some embodiments, the film or coating has a viscosity less than about 2% and / or less than about 1.19 g / m 2 The hot oil has a temperature of about 65° C. In some embodiments, the film or coating has a weight gain of less than about 3% and / or less than about 1.8 g / m 2 when contacted with room temperature oil for 15 hours. 2 of weight increase.

[0064] In some embodiments, the film or coating has a g / m2 / day of less than 50 g / m2 / day. 2 .mm / day), optionally less than 15g / m 2 .mm / day water vapor transmission rate (WVTR). In some embodiments, the film or coating has a water vapor transmission rate of about 0.3 grams per cubic centimeter (g / cm 3 ) to about 2.1 g / cm 3 In some embodiments, the film or coating has a tensile index of about 30 Newton meters per gram (Nm / g) or greater. In some embodiments, the film or coating has a stretchability of about 1.5% or greater.

[0065] In some embodiments, the packaging material is a food or beverage packaging material. In some embodiments, the packaging material further comprises a substrate, wherein the substrate is coated with a film or coating comprising A-MFC on at least one surface, optionally wherein the substrate is a flexible substrate. In some embodiments, the substrate comprises paper or another biodegradable and / or sustainable material, optionally wherein the paper comprises or consists of papermaking fibers derived from waste biomass.

[0066] In some embodiments, the presently disclosed subject matter provides a method for preparing a film having a viscosity less than about 5 percent (%) and / or less than about 2.5 grams per square meter (g / m2) when contacted with hot oil for 20 minutes. 2), wherein the hot oil has a temperature of about 65 degrees Celsius (° C.), the method comprising: (a) preparing a suspension comprising agro-based microfibrillated cellulose (A-MFC), wherein the A-MFC is microfibrillated cellulose (MFC) prepared from pulp from a non-wood lignocellulosic feedstock; (b) using the suspension to form a web; and (c) drying the web, thereby providing a film. In some embodiments, the non-wood lignocellulosic feedstock comprises one or more agricultural residues and / or industrial byproducts, optionally wherein the non-wood lignocellulosic feedstock comprises hemp stalk cores, a mixture of hemp stalk cores and hemp bast, cocoa pod shells, or a combination thereof.

[0067] In some embodiments, preparing a suspension comprising A-MFC comprises fibrillating a suspension of pulp from a non-wood lignocellulosic feedstock, wherein the pulp has a primary fines level of more than 10%, optionally wherein the pulp has a primary fines level of about 15% to about 50%. In some embodiments, the pulp is kraft pulp, autohydrolyzed pulp, unbleached pulp, higher yield pulp, or pulp containing higher lignin. In some embodiments, the method further comprises chemically modifying the pulp in an aqueous medium prior to fibrillation. In some embodiments, chemically modifying the pulp comprises carboxymethylating pulp, oxidizing pulp, or carboxymethylating and oxidizing pulp. In some embodiments, the method comprises carboxymethylating the pulp before or after fibrillation.

[0068] In some embodiments, preparing a suspension comprising A-MFC comprises contacting A-MFC with a liquid, optionally water, to provide a suspension comprising a total solids content of at least about 50 weight percent (wt%) A-MFC, optionally providing a suspension comprising a total solids content of about 50 wt% to about 80 wt% A-MFC. In some embodiments, the suspension has a solids content of about 2.0% or more and / or about 5% or less. In some embodiments, the suspension comprising A-MFC further comprises one or more of chitosan, cationic starch, glycerol, triethyl citrate, polyhydroxyalkanoate (PHA), and alkyl ketene dimer (AKD). In some embodiments, preparing the suspension comprises mixing the suspension at a temperature between about room temperature and about 80 degrees Celsius (°C) for a period of time, optionally about 30 minutes.

[0069] In some embodiments, step (b) comprises casting a web from the suspension. In some embodiments, the method further comprises applying the film to a surface of a substrate, optionally a paper substrate, to provide a film-coated substrate. In some embodiments, the method further comprises forming a packaging material from the film or from a film-coated substrate.

[0070] Therefore, one object of the presently disclosed subject matter is to provide a packaging material comprising A-MFC prepared from agro-based pulp and a method for preparing the same. This object and other objects are achieved in whole or in part by the presently disclosed subject matter.

[0071] Having stated the objects of the presently disclosed subject matter above, other objects and advantages of the presently disclosed subject matter will become apparent to one of ordinary skill in the art upon examination of the following description of the presently disclosed subject matter and the non-limiting accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0072] Figure 1 Composite diagram showing the production of microfibrillated cellulose (MFC) using a Masuko grinder, including photographic images and schematic diagrams.

[0073] Figure 2A and 2B The graph shows the Fourier transform infrared (FTIR) spectra of different fibers (percent (%) transmittance versus wave number (in centimeters (cm) -1 )count)). Figure 2A Shown from bottom to top are spectra of unmodified hemp core fiber (HH), HH modified by carboxymethylation (CM-HH), HH modified by carboxymethylation followed by periodate oxidation (CMPI-HH), and HH modified by periodate oxidation (PI-HH). Figure 2B Shown are the spectra of HH, hardwood fiber modified by carboxymethylation (CM-HW), and CM-HH.

[0074] Figure 3 The graph shows the relative degree of substitution (DS) of carboxymethylation for different fiber samples: hemp core modified by carboxymethylation (CM-HH); hemp mixture modified by carboxymethylation (HM); hardwood modified by carboxymethylation (HW); and hemp core carboxymethylated with a higher amount of sodium monochloroacetic acid salt (i.e., compared to the amount of sodium monochloroacetic acid salt used to carboxymethylate the other samples) (CM2-HH).

[0075] Figure 4The figure shows the percentage of primary fine fibers in various treated and untreated fibers before preparing microfibrillated cellulose (MFC) from the fibers. The left axis shows the average fiber length (in millimeters (mm)) of fibers from the following sources, while the right axis shows the primary fine fiber percentage (%) of fibers from the following sources: hemp stalk core (HH), HH modified by carboxymethylation (CM-HH), HH modified by periodate oxidation (PI-HH), unrefined hardwood (HW (unrefined)), refined hardwood (HW (2.5rev-PFI)), unrefined softwood (SW (unrefined)), refined softwood (SW (5krev-PFI)) and cocoa pod shell (CPH). Fine fiber % (bars) and fiber length values ​​(dashed lines) are also provided in the chart below the figure.

[0076] Figure 5 The graph shows the energy consumption during the microfibrillation process of various modified and unmodified fibers and the fine fiber level of the resulting microfibrillated cellulose (MFC). The energy consumption (in kilowatt-hours / ton (KWH / T)) is shown in the left axis and the percentage (%) of fine fibers is shown in the right axis. Values ​​are provided for MFC prepared from hemp stalk core (HH-MFC), MFC prepared from hemp stalk core (HH) modified by carboxymethylation (CM-HH-MFC), MFC prepared from HH modified by enhanced chemical carboxymethylation (CM2-HH-MFC), MFC prepared from HH modified by periodate oxidation (PI-HH-MFC), MFC prepared from HH modified by carboxymethylation and periodate oxidation (CMPI-HH-MFC), MFC prepared from a hemp mixture modified by carboxymethylation (CM-HM-MFC), MFC prepared from hardwood (HW) fibers modified by carboxymethylation (CM-HW-MFC), and MFC prepared from cocoa pod shells (CPH-MFC). Fines % (dashed line) and energy consumption (bars) are also provided in the chart below the figure.

[0077] Figure 6 Figure shows fiber length (in millimeter (mm)) and fines percentage (%) in various modified and unmodified fibers before or after microfibrillation. Provide fiber (HH) from hemp stalk core, fiber (CM-HH) from HH modified by carboxymethylation, microfibrillated cellulose (MFC) (CM-HH-MFC) prepared by CM-HH, HH (PI-HH) modified by periodate oxidation, MFC (PI-HH-MFC) from PI-HH, enhanced chemical CM-HH (CM2-HH), MFC (CM2-HH-MFC) prepared by CM2-HH and MFC (CPH-MFC) prepared by cocoa pod shell. Fines % (bar) and fiber length value (dashed line) are also provided in the chart under the figure.

[0078] Figure 7 Graph of the viscosity (in centipoise (cP)) of different microfibrillated cellulose (MFC), including MFC prepared from hemp wick (HH) modified by carboxymethylation (CM-HH-MFC), MFC prepared from HH modified by periodate oxidation (PI-HH-MFC), and MFC prepared from HH modified by carboxymethylation and periodate oxidation (CMPI-HH-MFC).

[0079] Figure 8 The graph shows the anionic charge (in microequivalents per liter (μeq / l)) of different microfibrillated celluloses (MFCs), including MFC prepared from a hemp mixture (HM) modified by carboxymethylation (CM-HM-MFC), MFC prepared from hardwood (HW) fibers modified by carboxymethylation (CM-HW-MFC), MFC prepared from hemp stalk core (HH) modified by carboxymethylation (CM-HH-MFC), MFC prepared from HH modified by periodate oxidation (PI-HH-MFC), MFC prepared from HH modified by enhanced chemical carboxymethylation (CM2-HH-MFC), and MFC prepared from HH modified by carboxymethylation and periodate oxidation (CMPI-HH-MFC).

[0080] Fig. 9 The graph shows the carboxyl content (in milliequivalents / 100 grams (mEq / 100 g)) of different microfibrillated celluloses (MFCs), including MFC prepared from a hemp mixture (HM) modified by carboxymethylation (CM-HM-MFC), MFC prepared from hardwood (HW) fibers modified by carboxymethylation (CM-HW-MFC), MFC prepared from hemp core (HH) modified by carboxymethylation (CM-HH-MFC), MFC prepared from HH modified by periodate oxidation (PI-HH-MFC), MFC prepared from HH modified by enhanced chemical carboxymethylation (CM2-HH-MFC), and MFC prepared from HH modified by carboxymethylation and periodate oxidation (CMPI-HH-MFC).

[0081] Fig.10The scanning electron microscope (SEM) image of the microfibrillated cellulose (MFC) sample prepared by unmodified and modified hemp stalk core fiber (HH) is shown.The image in the left column is the image of the MFC (HH-MFC) prepared by unmodified hemp stalk core, the image in the second column from the left is the image of the MFC (CM-HH-MFC) prepared by the carboxymethylated hemp stalk core, the image in the second column from the right is the image of the mixture (CM-PI-HH-MFC) of the MFC prepared by the carboxymethylated hemp stalk core and the MFC prepared by the hemp stalk core oxidized by periodate, and the image in the right column is the image of the MFC (PI-HH-MFC) prepared by the hemp stalk core oxidized by periodate.Image is taken with three different magnifications: 500 times magnification (500x, upper row), 1000 times magnification (1000x, middle row) and 5000 times magnification (5000x, lower row).

[0082] Fig.11 Shown is the transmission electron microscope (TEM) image of the MFC sample made of unmodified and modified hemp stalk core fiber.From left to right, image is the image of MFC (HH-MFC) prepared by unmodified hemp stalk core, the image of MFC (CM-HH-MFC) prepared by carboxymethylated hemp stalk core, the image of the mixture (CM-PI-HH-MFC) of MFC prepared by carboxymethylated hemp stalk core and the MFC prepared by periodate oxidized hemp stalk core and the image of MFC (PI-HH-MFC) prepared by periodate oxidized hemp stalk core.For all samples, image is taken with 5000 times (5000x) magnification.The scale bar in the lower left corner of each image represents 2 microns (μm).

[0083] Fig.12 The schematic diagram includes a series of photographic images showing the workflow of a process for preparing coated films from microfibrillated cellulose via a solvent casting method.

[0084] Figures 13A-13E The graph shows the viscosity (in centipoise (CPS)) of different coating / film formulations containing various types of biopolymers at different revolutions per minute (rpm). Fig.13AThe viscosity of aqueous formulations prepared from the following solid mixtures is shown: a solid mixture containing 100% microfibrillated cellulose (MFC) prepared from hemp stalk core (HH-MFC) mixed at 80 degrees Celsius (°) (HH-MFC (100)-80T) (data are shown by circles and solid line); a solid mixture containing 80% HH-MFC and 20% chitosan (CH) mixed at 80 degrees Celsius (HH-MFC (80)-CH (20)-80T) (data are shown by diamonds and dots). line); a solid mixture containing 80% HH-MFC, 20% CH and 2% glycerol (GL) mixed at 80 degrees Celsius (HH-MFC(80)-CH(20)-GL(2)-80T) (data shown by triangles and solid lines); and a solid mixture containing 80% HH-MFC, 20% CH and 2% GL mixed at room temperature (RT) (HH-MFC(80)-CH(20)-GL(2)-RT) (data shown by squares and dashed lines). Fig. 13B The viscosity of aqueous formulations prepared from the following solid mixtures is shown: a solid mixture comprising 80% microfibrillated cellulose prepared from hemp stalk core modified by carboxymethylation (CM-HH-MFC), 20% chitosan and 2% glycerol and mixed at room temperature (CM-HH-MFC(80)-CH(20)-GL(2)-RT) (data are shown by circles and solid lines); a solid mixture comprising 80% CM-HH-MFC, 20% chitosan and 2% glycerol and mixed at 80 degrees Celsius (CM -HH-MFC(80)-CH(20)-GL(2)-80T) (data shown by circles and dashed lines); a solid mixture containing 80% CM-HH-MFC and 20% chitosan mixed at 80 degrees Celsius (CM-HH-MFC(80)-CH(20)-80T) (data shown by diamonds and dashed lines); and a solid mixture containing 100% CM-HH-MFC mixed at 80 degrees Celsius (CM-HH-MFC-80T) (data shown by triangles and dotted lines). Fig. 13CThe viscosity of aqueous formulations prepared from the following solid mixtures is shown: a solid mixture containing 80% microfibrillated cellulose derived from hemp stalk core modified by carboxymethylation followed by periodate oxidation (CMPI-HH-MFC), 20% chitosan and 2% glycerol mixed at 80 degrees Celsius (CMPI-HH-MFC-(80)-CH(20)-GL(2)-80T) (data shown by triangles and dotted lines); a solid mixture containing 80% CMPI-HH-MFC, 20% chitosan and 2% glycerol mixed at room temperature (CMPI-HH-MFC(80)-CH(20)-GL(2)-RT) (data are shown by circles and solid lines); a solid mixture containing 80% CMPI-HH-MFC and 20% chitosan mixed at 80 degrees Celsius (CMPI-HH-MFC(80)-CH(20)-80T) (data are shown by squares and solid lines); and a solid mixture containing 100% CMPI-HH-MFC mixed at 80 degrees Celsius (CMPI-HH-MFC100-80T) (data are shown by diamonds and solid lines). Fig.13D The viscosity of aqueous formulations prepared from the following solid mixtures is shown: a solid mixture containing 80% microfibrillated cellulose from cocoa pod shells (CPH-MFC), 20% chitosan and 2% glycerol mixed at 80 degrees Celsius (CPH-MFC(80)-CH(20)-GL(2)-80T) (data shown by squares and dotted lines); a solid mixture containing 80% CPH-MFC and 20% chitosan mixed at 80 degrees Celsius (CPH-MFC(80)-CH(20)-GL(2)-80T); and a solid mixture containing 80% CPH-MFC and 20% chitosan mixed at 80 degrees Celsius. 0)-CH(20)-80T) (data shown by circles and solid line); a solid mixture containing 80% CPH-MFC, 20% chitosan and 2% glycerol mixed at room temperature (CPH-MFC(80)-CH(20)-GL(2)-RT) (data shown by diamonds and solid line); and a solid mixture containing only 100% CPH-MFC solid mixed at 80 degrees Celsius (CPH-MFC(100)-80T) (data shown by triangles and solid line). Fig.13EThe viscosity of aqueous formulations prepared from the following solid mixtures is shown: a solid mixture containing 80% cocoa pod husk fiber, 20% chitosan and 2% glycerol mixed at room temperature (CPH fiber (80)-CH(20)-GL(2)-RT) (data shown by circles and solid line); a solid mixture containing 80% cocoa pod husk fiber, 20% chitosan and 2% glycerol mixed at 80 degrees Celsius (CPH fiber (80)-CH(20)-GL(2)-RT) (data shown by circles and solid line); 20)-GL(2)-80T) (data are shown by squares and solid lines); a solid mixture comprising 80% cocoa pod husk fiber and 20% chitosan mixed at 80 degrees Celsius (CPH fiber (80)-CH(20)-80T) (data are shown by triangles and dashed lines); and a solid mixture comprising 100% cocoa pod husk fiber mixed at 80 degrees Celsius (CPH fiber (100)-80T) (data are shown by diamonds and dotted lines).

[0085] Figures 14A-14D The graph shows the bulk volume (cm3 / g (cm3) of films prepared from various modified and unmodified microfibrillated cellulose (MFC) or pulp formulations. 3 / g)). Fig.14A The bulk volume of films prepared from formulations containing: MFC prepared from unmodified hemp stalk core (HH) and cocoa pod shell (CPH); CPH pulp fiber (CPH-fiber); or MFC from carboxymethylated fiber (CM-MFC). Some formulations also contained 20% chitosan (CH) and 2% glycerol (GL) based on the solid mixture. These formulations were all mixed at 80 degrees Celsius (80F). Fig. 14B The bulk volume of films prepared from formulations containing (left) MFC from unmodified hemp mixture (HM), HH, CPH, unbleached CPH (UCPH) or autohydrolyzed hemp stalk core (AH-HH) or (right) MFC from carboxymethylated hemp mixture (CM-HM-MFC) or MFC from HM carboxymethylated followed by periodate oxidation (CMPI-HM-MFC). Some formulations were based on solid mixtures containing 50% or 20% chitosan (CH), 20% CH and 1% alkyl ketene dimer (AKD) or 45% CH and 5% glycerol (GL) and prepared at room temperature (RT) or 80 degrees Celsius (80F). Fig. 14CThe bulk volume of films prepared from formulations containing (left) MFC from unmodified HH (HH-MFC), or (right) MFC from carboxymethylated hemp stalk core (CM-HH-MFC), MFC from carboxymethylated hemp mixture (CM-HM-MFC). Some formulations were based on solid mixtures containing 20% ​​chitosan (CH) or 20% CH in combination with 1% glycerol (GL) and prepared at room temperature (RT) or 80 degrees Celsius (80F). Fig.14D The bulk volumes of films prepared from formulations based on solid mixtures are shown: (left) solid mixtures containing 80% unmodified MFC derived from HH, 20% cationic starch (St) or 20% CH and 2% GL at RT or 80T; (middle) solid mixtures containing 80% MFC prepared from carboxymethylated HH (i.e., CM-HH-MFC) with 20% St or 20% CH and 2% GL at RT or 80T; and (right) solid mixtures containing 80% CM-HH-MFC and 20% MFC prepared from periodate-oxidized hemp stalk cores (PI-HH-MFC) with or without 20% St or 20% CH and 2% GL at RT.

[0086] Figures 15A-15C Shown are scanning electron micrograph (SEM) images of membranes prepared from different formulations of microfibrillated cellulose (MFC). Fig.15A A series of SEM images of films prepared from formulations comprising: MFC from unmodified hemp stalk core (HH or HH-MFC); MFC from carboxymethylated hemp stalk core (CM-HH-MFC); a mixture of MFC from carboxymethylated hemp stalk core and MFC from periodate-oxidized hemp stalk core (CM-PI); or MFC from carboxymethylated and periodate-oxidized hemp stalk core (CMPI). Some formulations also comprise one or more of cationic starch (St), chitosan (CH) and glycerol (GL). Formulations were prepared at 80 degrees Celsius (80) or room temperature (RT). Images were magnified 100 times (100x). Fig. 15B A pair of SEM images showing films prepared from a formulation comprising carboxymethylated hemp core, chitosan and glycerol (CM-HH-MFC(80)-CH(20)-GL(20)-RT) at room temperature. The left image is at 100 times magnification, while the right image is at 1000 times (1000x). Fig. 15C A pair of SEM images showing the Fig. 15BThe membranes were prepared using a formulation of the same composition as the formulation, but wherein the formulation was prepared at 80 degrees Celsius (CH-HH-MFC(80)-CH(20)-GL(2)-80T). The left side is an image at 100 times magnification, while the right side is an image at 1000 times (1000x) magnification.

[0087] Figures 16A-16D The graph shows Fourier transform infrared (FTIR) spectra (percent (%) transmittance versus wave number (in inverse centimeters (cm)) of different polymers, microfibrillated cellulose (MFC), MFC composites and MFC composites with chitosan (CH), CH and glycerol (GL or GLY) or with cationic starch (ST) and GL. -1 )count)). Fig.16A Shown are FTIR spectra of CH and composites prepared from formulations comprising MFC derived from unmodified hemp stalk core (HH-MFC) with or without CH or CH and GLY, wherein the formulations were prepared at room temperature (RT) or 80 degrees Celsius (80F). Fig. 16B Shown are FTIR spectra of CH and composites prepared from formulations containing MFC derived from carboxymethylated hemp stalk core (CM or CM-MFC) with or without CH or CH and GLY at RT or 80T. Fig. 16C The following FTIR spectra are shown: chitosan; MFC prepared from periodate-oxidized hemp stalk core (PI-HH); composite materials prepared from a formulation comprising a mixture of MFC prepared from periodate-oxidized hemp stalk core and MFC prepared from carboxymethylated hemp stalk core (CM-PI); composite materials prepared from a formulation comprising CM-PI, CH and GY; and composite materials prepared from a formulation comprising CM-PI-ST and GL. The formulations for the composite materials were prepared at room temperature (RT). Fig.16D The figure shows FTIR spectra of cationic starch (ST) and composites prepared from the following formulations: formulations containing MFC (HH) prepared from unmodified hemp stalk cores, ST and GL (HH-ST-GL-RT and HH-ST-GL-80T) at room temperature (RT) or at 80 degrees Celsius; formulations containing MFC (CM), ST and GL from carboxymethylated hemp stalk cores (CM-ST-GL-RT and CM-ST-GL-80T) at RT or 80 degrees Celsius; or formulations containing a mixture of MFC from periodate-oxidized hemp stalk cores and MFC from carboxymethylated hemp stalk cores (CM-PI), ST and GL at RT (CM-PI-ST-GL-RT).

[0088] Fig.17 Schematic diagram showing the formation of a network between carboxymethyl cellulose and chitosan.

[0089] Fig.18 is a series of photographic images showing the steps for conducting hot oil absorption testing on films of the presently disclosed subject matter and possible results of the testing.

[0090] Figures 19A-19D The figure shows the performance of different membranes made of various modified and unmodified microfibrillated cellulose (MFC) composites in hot oil tests ( Fig.19A and 19B ) and room temperature oil test ( Fig.19C and 19D ) in the weight gain. The weight gain is expressed as a percentage (%) of the original film weight ( Fig.19A and 19C ) or grams per square meter (gsm, Fig.19B and 19D ) to measure. Fig.19A and 19B Data from films prepared from the following formulations are shown: (left) formulations containing 100% unmodified hemp core MFC (HH-MFC) at room temperature (RT) or 80 degrees Celsius (80T); formulations containing 80% HH-MFC and 20% chitosan (CH) or formulations containing 80% HH-MFC, 20% CH or cationic starch (ST) and 1% glycerol (GL); (middle) formulations containing 100% carboxymethylated hemp at RT or 80T. stalk core (CM-HH-MFC), a formulation containing 80% CM-HH-MFC and 20% CH, or a formulation containing 80% CM-HH-MFC, 20% CH or ST and 1% GL; and (right) a formulation containing CM-HH-MFC and a mixture of MFC from periodate-oxidized hemp stalk core (PI-HH-MFC), a formulation containing a mixture of modified MFC and CH, or a formulation containing a mixture of modified MFC and ST. Fig.19C and 19DThe weight gain in films produced from the following formulations is shown: a formulation comprising 50% MFC from autohydrolyzed hemp stalk core (AH-HH-MFC) and 50% CH prepared at room temperature (AH-HH-MFC(50)-CH(50)-RT); a formulation comprising MFC from unbleached cocoa pod shells (UCPH); a formulation comprising 50% UCPH and 50% CH prepared at RT (UCPH-MFC(50)-CH(50)-RT), a formulation comprising 80% CM-HH-MFC and 20% CH prepared at 80 degrees Celsius (CM-HH-MFC(80)-CH(20)-80C), a formulation comprising 50% MFC from cocoa pod shells and 50% CH prepared at 80 degrees Celsius (CPH-MFC(50)-CH(50)-80C), a formulation comprising MFC from carboxymethylated and periodate prepared at 80 degrees Celsius (CPH-MFC(50)-CH(50)-80C). Formulations of MFC from oxidized hemp stalk core (CMPI-HH), a formulation containing 50% CMPI-HH and 50% CH prepared at room temperature (CMPI-HH(50)_CH(50)_RT), a formulation containing MFC from a carboxymethylated cannabis mixture (CM-HM-MFC), a formulation containing 50% MFC from a cannabis mixture and 50% CH prepared at RT (HM-MFC(50)-CH(50)-RT), a formulation containing 80% MFC from a cannabis mixture and 20% CH prepared at RT (HM-MFC(80)-CH(20)-RT) and a formulation containing 80% MFC from a cannabis mixture and 20% CH and 1% alkyl ketene dimer (AKD) prepared at 80 degrees Celsius (HM-MFC(80)-CH(20)-AKD(1)-80C).

[0091] Figures 20A-20F The figure shows that ( Figures 20A-20D ) Water vapor transmission rate (WVTR) of films prepared from formulations made from various modified and unmodified microfibrillated cellulose (MFC), ( Fig.20E ) different membrane densities and ( Fig.20F )Relationship between density and WVTR. Fig. 20A The WVTR of composite films prepared from formulations containing: (left) unmodified MFC from hemp stalk core (HH-MFC) or unmodified MFC from cocoa pod shell (CPH-MFC); (middle) cocoa pod shell pulp fiber (CPH fiber); and (right) MFC from carboxymethylated material (CM-MFC). These formulations were all mixed at 80 degrees Celsius (80F). Some formulations also contained chitosan (CH) or CH and glycerol (GL). Fig. 20BThe WVTR of composite films prepared from formulations containing the following is shown: MFC from a hemp mixture (HM-MFC); MFC from hemp stalk core (HH-MFC); MFC from CPH; MFC from unbleached CPH (UCPH-MFC); MFC from autohydrolyzed hemp stalk core (AH-HH-MFC); MFC from a carboxymethylated hemp mixture (CM-HM-MFC); MFC from a hemp mixture carboxymethylated followed by periodate oxidation (CMPI-HM-MFC); MFC from carboxymethylated CPH (CM-CPH-MFC). These formulations were mixed at room temperature (RT) or 80F. Some formulations contained CH, CH and GL or CH and alkyl ketene dimer (AKD). Fig. 20C Shown are the WVTRs of films prepared from formulations containing: (left) MFC from unmodified hemp stalk core (HH-MFC) or (right) carboxymethylated MFC. The formulations were mixed at RT or 80T. Some formulations contained CH and GL. Fig.20D Shown are WVTRs of films prepared from formulations comprising: (left) MFC from hemp stalk core (HH-MFC); (middle) MFC from carboxymethylated hemp stalk core (CM-HH-MFC); and (right) a mixture of CM-HH-MFC and MFC from periodate-oxidized hemp stalk core (PI-HH-MFC). These formulations were mixed at RT or 80T. Some formulations included CH and GL or cationic starch (ST) and GL. Fig.20E The density of films prepared from formulations containing (left) MFC from a hemp mixture (HM-MFC) and (right) MFC prepared from hemp stalk core (HH-MFC) are compared. WVTR is expressed in g / m2 mm / day (g / m 2 .mm / day), density is expressed in grams / cubic centimeter (g / cm 3 )express.

[0092] Fig.21A and 21B Photographic images of the results of the kit testing the membrane's resistance to oil and grease. Fig.21A Shown are exemplary results observed when the membrane was tested by the kit, and Fig. 21B Shown are exemplary results observed when a membrane fails the kit test.

[0093] Fig. 22 is a series of photographic images illustrating the workflow for evaluating the oil and grease resistance of the presently disclosed films after creasing.

[0094] Figures 23A-23C Photographic images of water resistance results for exemplary films of the presently disclosed subject matter. Fig.23AFigure 2 shows an image showing the dispersion of a film made of 100% unmodified cocoa pod husk (CPH) microfibrillated cellulose (MFC) (CPH-MFC(100)-80T) prepared at 80 degrees Celsius in water after two hours. Fig. 23B Images showing that membranes made from carboxymethylated hemp core MFC (CM-HH-MFC) remained intact after 7 days in water. Fig.23C Images showing that the CM-HH-MFC membrane remained intact after 32 days in water.

[0095] Fig.24 Graph showing the air resistance (measured in Gurley seconds) of different films comprising cocoa pod shell (CPH) fibers and microfibrillated cellulose from cocoa pod fibers (CPF-MFC): a film made from 100% CPH fibers at 80 degrees Celsius (CPH-fiber (100)-80T); a film made from 80% CPH-fibers and 20% chitosan (CH) at 80 degrees Celsius (CPH-fiber (80)-CH(20)-80T); a film made from 80% CPH fibers, 20% CH and 2% glycerol (GL) at 80 degrees Celsius (CPH-fiber (80)-CH(20)-GL(2)-80T); and a film made from 80% CPH-MFC, 20% CH and 2% GL at room temperature (CPH-MFC(80)-CH(20)-GL(2)-RT).

[0096] Figures 25A-25D A series of graphs showing the tensile properties of different films made from various modified and unmodified microfibrillated cellulose (MFC) fiber composites. The tensile index (tensile strength divided by basis weight) is reported in Newton meters per gram (Nm / g). Fig.25A The tensile index of composite films prepared from formulations containing: (left) unmodified MFC from hemp stalk core (HH-MFC) or unmodified MFC from cocoa pod shell (CPH-MFC); (middle) cocoa pod shell pulp (CPH fiber); and (right) MFC from modified hemp stalk core (CM-HH-MFC). These formulations were all mixed at 80 degrees Celsius (80F). Some formulations also contained chitosan (CH) or CH and glycerol (GL). Fig.25BThe tensile index of composite films prepared from the following formulations is shown: MFC from a hemp mixture (HM-MFC); MFC from a hemp stalk core (HH-MFC); MFC from CPH (CPH-MFC); MFC from unbleached CPH (UCPH-MFC); MFC from an autohydrolyzed hemp stalk core (AH-HH-MFC); MFC from a carboxymethylated hemp mixture (CM-HM-MFC); or MFC from a hemp mixture oxidized with periodate followed by carboxymethylation (CMPI-HM-MFC). These formulations were mixed at room temperature (RT) or 80 degrees Celsius (80F). Some formulations contained CH, CH and GL or CH and alkyl ketene dimer (AKD). Fig.25C The tensile index of films prepared from formulations containing (left) MFC from unmodified hemp stalk core (HH-MFC) or (right) carboxymethylated MFC (CM-HH-MFC) are shown. The formulations were mixed at RT or 80T. Some formulations contained CH or CH and GL. Fig.25D The tensile index of films prepared from formulations comprising: (left) MFC from unmodified hemp stalk core (HH-MFC); (middle) MFC from carboxymethylated hemp stalk core (CM-HH-MFC); and (right) a mixture of CM-HH-MFC and MFC from periodate-oxidized hemp stalk core (PI-HH-MFC). These formulations were mixed at RT or 80T. Some formulations included CH and GL or cationic starch (ST) and GL.

[0097] Figures 26A-26D is a series of graphs showing the elongation (in percent (%)) of different films made from various modified and unmodified microfibrillated cellulose (MFC) composites. Fig.26A The tensile strength of composite films prepared from formulations containing: (left) unmodified MFC from hemp stalk core (HH-MFC) or unmodified MFC from cocoa pod shell (CPH-MFC); (middle) cocoa pod shell pulp (CPH fiber); and (right) MFC from carboxymethylated material (CM-MFC). These formulations were all mixed at 80 degrees Celsius (80F). Some formulations also contained chitosan (CH) or CH and glycerol (GL). Fig.26BThe tensile strength of composite films prepared from formulations comprising: MFC from a hemp mixture (HM-MFC); MFC from a hemp stalk core (HH-MFC); CPH-MFC; MFC from unbleached CPH (UCPH-MFC); MFC from an autohydrolyzed hemp stalk core (AH-HH-MFC); MFC from carboxymethylated fiber (CM-MFC); MFC from a carboxymethylated hemp mixture (CM-HM-MFC); or MFC from a hemp mixture oxidized with periodate followed by carboxymethylation (CMPI-HM-MFC). These formulations were mixed at room temperature (RT) or 80F. Some formulations contained CH, CH and GL or CH and alkyl ketene dimer (AKD). Fig.26C Shown are the elongation of films prepared from formulations containing: (left) MFC from unmodified hemp stalk core (HH-MFC) or (right) carboxymethylated MFC. These formulations were mixed at RT or 80T. Some formulations contained CH or CH and GL. Fig.26D Shown are the tensile strengths of films prepared from formulations comprising: (left) MFC from unmodified hemp stalk core (HH-MFC); (middle) MFC from carboxymethylated hemp stalk core (CM-HH-MFC); and (right) a mixture of CM-HH-MFC and MFC from periodate-oxidized hemp stalk core (PI-HH-MFC). These formulations were mixed at RT or 80T. Some formulations included CH and GL or cationic starch (ST) and GL. DETAILED DESCRIPTION

[0098] The presently disclosed subject matter will now be described more fully hereinafter with reference to the accompanying drawings, in which representative embodiments are shown. However, the presently disclosed subject matter may be embodied in different forms and should not be construed as being limited to the embodiments described herein. Instead, these embodiments are provided so that the present disclosure will be comprehensive and complete, and will fully convey the scope of the embodiments to those skilled in the art.

[0099] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the presently disclosed subject matter belongs. All publications, patent applications, patents, and other references mentioned herein are incorporated by reference in their entirety.

[0100] Throughout the specification and claims, a given chemical formula or name shall encompass all optical and stereoisomers, as well as the racemic mixtures where such isomers and mixtures exist.

[0101] I. Definitions

[0102] While it is believed that the following terms are well understood by those of ordinary skill in the art, the following definitions are set forth to facilitate explanation of the presently claimed subject matter.

[0103] Following long-standing patent law convention, the terms "a," "an," and "the" when used herein, including the claims, mean "one or more."

[0104] As used herein, when referring to a value or amount, for example, relative to another measurement, the term "about" is meant to encompass variations of ±20%, ±10%, ±5%, ±1%, and ±0.1% from the specified value or amount in some embodiments, as such variations are appropriate. The term "about" can be applied to all values ​​set forth herein.

[0105] As used herein, when used in the context of a list of entities, the term "and / or" refers to the entities as being present either alone or in combination. Thus, for example, the phrase "A, B, C, and / or D" includes A, B, C, and D individually, but also includes any and all combinations and subcombinations of A, B, C, and D.

[0106] The term "comprising," which is synonymous with "including," "containing," or "characterized by," is inclusive or open-ended and does not exclude additional, unrecited elements or method steps. "Comprising" is a technical term used in claim language that means the named elements are present, but other elements may be added and still form a construction or method within the scope of the claim.

[0107] As used herein, the phrase "consisting of" excludes any element, step, or ingredient not specified in a claim. When the phrase "consisting of" appears in the body clause of a claim rather than immediately following a preamble, it is limited only to the elements set forth in that clause; other elements are not excluded from the claim as a whole.

[0108] As used herein, the phrase "consisting essentially of" limits the scope of a claim to the specified materials or steps, and those materials or steps that do not materially affect the basic and novel characteristics of the claimed subject matter.

[0109] With respect to the terms "comprising," "consisting of," and "consisting essentially of," where one of these three terms is used herein, the presently disclosed and claimed subject matter may encompass the use of either of the other two terms.

[0110] As used herein, "significance" or "significant" refers to a statistical analysis of the probability that a non-random association exists between two or more entities. In order to determine whether a relationship is "significant" or has "significance", statistical manipulation of the data can be performed to calculate the probability, expressed as a "p-value" in some embodiments. Those p-values ​​below a user-defined cutoff point are considered significant. In some embodiments, p-values ​​less than or equal to 0.05, in some embodiments less than 0.01, in some embodiments less than 0.005, and in some embodiments less than 0.001 are considered significant.

[0111] As used herein, ranges can be expressed as from "about" one specific value and / or to "about" another specific value. It is also understood that multiple values ​​are disclosed herein, and each value is also disclosed herein as including "about" the value in addition to the specific value itself. For example, if the value "10" is disclosed, then "about 10" is also disclosed. It is also understood that every unit between two specific units is also disclosed. For example, if 10 and 15 are disclosed, then 11, 12, 13, and 14 are also disclosed.

[0112] As used herein, "paper" refers to a material consisting of cellulose fibers and / or lignocellulose fibers that are dehydrated, pressed and dried together in an aqueous medium (mainly water). For example, paper can include a web of cellulose fibers and / or lignocellulose fibers with a top side and a bottom side. In some embodiments, paper is a planar sheet. In some embodiments, the sheet can have a thin (e.g., less than about 5mm) edge. Alternatively, paper can be molded into any desired shape. In some embodiments, paper can be flexible. In some embodiments, paper can be inextensible so that it maintains its shape and structure during being commonly used as a packaging material such as a food packaging product.

[0113] As used herein, the term "papermaking fiber" refers to cellulose fibers and / or lignocellulosic fibers and fiber mixtures including cellulose fibers and / or lignocellulosic fibers. Papermaking fibers include non-wood fibers, such as but not limited to cotton, abaca, bamboo, banana, kenaf, grass, flax, straw, jute, hemp, bagasse, milkweed floss, cocoa pod shells and pineapple leaf fibers and derivatives thereof, and wood fibers, such as wood fibers obtained from deciduous trees and conifers, including softwood fibers, such as pine, fir, spruce, cedar, larch, etc., hardwood fibers, such as eucalyptus, maple, birch, poplar, oak, etc. In some embodiments, papermaking fibers are fibers from agricultural and / or industrial waste biomass, such as hemp stalk core, a mixture containing hemp stalk core and hemp bast fibers, and cocoa pod shells. Papermaking fibers may be released from their source materials by chemical and / or mechanical pulping processes known in the art, such as, but not limited to, kraft (sulfate) and sulfite chemical pulping processes (in which most of the lignin and hemicellulose components are removed), solvent pulping (ethanol-water, organic acids, SO2-ethanol-water, etc.), semi-chemical pulping, enzymatic pulping, chemical thermomechanical pulping (CTMP), thermomechanical pulping (TMP), hydrothermal pulping, autohydrolysis or hydrothermal pulping, other alkaline (e.g., soda or carbonate) pulping, or any combination of chemical and / or mechanical treatments. Bleaching chemicals such as hydrogen peroxide, oxygen, sodium hydroxide, enzymes, chlorine dioxide, hypochlorite, ozone, peracids, and / or other bleaching agents may be used to whiten the "cellulosic material." Suitable bleaching techniques may include elemental chlorine-free (ECF) or total chlorine-free (TCF) bleaching.

[0114] The terms "pulping" and "defibration" refer to the process of releasing discrete fibers from a cellulosic or lignocellulosic feedstock.

[0115] "Furnish" and other terms refer to an aqueous composition comprising lignocellulosic fibers and optionally additives, such as those commonly used in papermaking, including dry strength additives, wet strength resins, etc. As used herein, the term "slurry" refers to an aqueous dispersion of lignocellulose. In some embodiments, the terms "furnish" and "slurry" can be used interchangeably.

[0116] As used herein, term " biomass " refers to the renewable organic material from plant.As used herein, term " discarded biomass " refers to the biomass material that is usually not fully utilized or not utilized and / or is regarded as low-value.Usually, " discarded biomass " is the by-product from agricultural or industrial process, which relates to gatherings or otherwise handles parent biomass material.Therefore, for example, discarded biomass (or in some embodiments " agricultural base ") refers to agricultural residues and the by-product of the processing of other plants.

[0117] As used herein, the term "hemp stalk core" refers to the inner core of the stem of hemp plant (hemp plant / Cannabis sativa), including relatively short woody fibers and stem pith. The hemp stalk core can be separated from the stem by a process known as "retting" or by a peeling process. As used herein, the term "hemp mixture" refers to a mixture of a hemp stalk core and the material from the outer ring of the hemp stem, which can include longer phloem (or "bast") fibers.

[0118] As used herein, the term "fines" refers to the portion of lignocellulosic particles in pulp or a mixture of lignocellulosic fibers that can pass through a 200 mesh screen or a perforated plate having a pore size of 76 micrometers (μm). The term "primary fines" refers to fines generated by pulping or by pulping and bleaching lignocellulosic raw materials. "Total fines" refers to the total amount of primary fines and "secondary fines", wherein "secondary fines" are fines generated by other pulp processing (e.g., refining and / or chemical modification).

[0119] As used herein, the term "microfibrillated cellulose" or "MFC" refers to cellulose fibers obtained by fibrillating a cellulose-based pulp. MFC fibers have a high aspect ratio, with an average fiber width in the nanometer range (e.g., between about 5 nm and about 500 nm) and a fiber length in the micrometer to millimeter range (e.g., between about 0.1 μm and about 1 mm or more). Carboxymethylated microfibrillated cellulose refers to MFC obtained by fibrillating a carboxymethylated cellulose-based raw material (e.g., pulp). In some embodiments, fibrillation is performed by mechanical treatment, as described below.

[0120] II. General Considerations

[0121] Paper is different from typical substrates, such as plastics, metals and glass, because the cellulose that is the main component of paper is relatively reactive under various chemical and thermal treatment conditions. It easily absorbs fluids, such as water, grease and oil. In addition, many air gaps and micropores in the fiber can allow moisture and gaseous substances to pass through the paper. Traditionally, papermakers rely on a large amount of refining and surface sizing agents (such as starch) to produce more closed paper. However, a large amount of refining may be difficult, especially for the feed composed of agricultural fibers (that is, fibers from agricultural raw materials), because their cellulose fine fiber content is high and a large amount of refining has an impact on drainage during the forming process. Even after these treatments, some micropores will still remain and provide undesirable fluid and gas flow. According to one aspect of the current disclosed theme, a new generation of flexible food packaging from agricultural-based fibers is described. In some embodiments, the packaging includes functional additives and / or chemically modified cellulose fibers to impart or improve mechanical and / or barrier properties.

[0122] Cellulose is the most abundant natural polymer on earth. The sustainable development of cellulose fibers from non-wood biomass has great potential to replace single-use synthetic plastics in packaging and other industrial applications. The valorization of plant-based fibers may provide a global platform for the development of eco-friendly food packaging and hygiene products. These types of bio-based products are recyclable and can play an important role in the circular economy. Among various packaging applications, food packaging is an important aspect of our daily life and current economy. As described above, packaging helps to enhance the value of food, for example, by reducing food waste and chemical pollution by maintaining food quality during storage, transportation and distribution, and by providing other useful characteristics (Edyta et al., 2015)(Gutta et al., 2013). However, the formability of cellulose paper is very limited due to its higher degree of deformation and lack of thermoplasticity compared to synthetic polymers, which limits its application (Fengel, 1992). Therefore, to date, paper-based materials cannot be widely utilized in high-quality industrial forming processes and are limited to simple geometric shapes.

[0123] In some embodiments, the subject matter disclosed herein relates to chemical modification of cellulose fibers to enhance their usability, for example, in the preparation of microfibrillated cellulose (MFC) for paper coating, packaging film and composite material development. More particularly, cellulose has three hydroxyl groups on each anhydroglucose unit (AGU), which can be chemically modified in various ways, as shown in Scheme 1 below. The presence of these chemically reactive hydroxyl groups can customize the functionality of cellulose fibers by modifications including acid hydrolysis, grafting and substitution reactions. Among various chemical modifications, acid hydrolysis can be used to cut the amorphous regions of cellulose fibers to synthesize cellulose nanocrystals (CNCs) (Ranby et al., 1949) (Elazzouzi-Hafraoui et al., 2008). Other modifications include etherification, which can be carried out under alkaline swelling conditions to obtain block copolymer substitution products, wherein regioselective homogeneous substitution (Landoll, 1982) (Heinze & Liebert, 2001) can be achieved in some solvents. The hydroxyl groups of cellulose can be selectively or non-selectively replaced with carboxylates, depending on the type of reagent selected and the type of hydroxyl groups involved (i.e., primary or secondary). The introduction of carboxyl groups can lead to further chemical modifications such as hydrophobization, crosslinking, and grafting, thereby imparting additional properties to the fiber. Exemplary chemical modifications of fibers include, but are not limited to, carboxymethylation, periodate oxidation, and (2,2,6,6-tetramethylpiperidin-1-yl)oxy (TEMPO)-mediated oxidation.

[0124]

[0125] Scheme 1: Potential chemical modification of cellulose fibers

[0126] Carboxymethyl cellulose (CMC) is one of the most commonly used cellulose ethers because of its low allergenicity and non-toxic properties. It has high viscosity and high surface charge availability, which will enhance its water absorption, thickening and film-forming ability. CMC is widely used in ice cream, toothpaste, detergents, fat-free products, textiles, etc. CMC can be prepared homogeneously and heterogeneously by changing the solvent system. A more sustainable CMC with a low degree of substitution (DS) can be generated using a homogeneous solvent system (e.g., water), while a heterogeneous solvent system (e.g., 2-propanol-water mixture or benzene-ethanol-water mixture) or a homogeneous organic solvent (e.g., butanol) is mainly used to prepare CMC with a higher DS (Zhao et al., 2003)(Moussa et al., 2019). For softwood fibers, a DS of 1.24 has been achieved, with a preferred substitution order of O6 ≥ O2 > O3, and a DS of 2.83 has been achieved by extensive and prolonged treatment of fig stem cellulose fibers using butanol as solvent (Heinze & Pfeiffer, 1999) (Moussa et al., 2019).

[0127] CMC can be prepared by reacting cellulose with a carboxymethylating agent such as chloroacetic acid (i.e., monochloroacetic acid (MCA)). See Scheme 2 below. The preparation of CMC generally involves an alkaline reaction environment to activate the cellulose hydroxyl groups, and sodium hydroxide (NaOH) or other alkali solutions have generally been used for this purpose. The degree of carboxymethylation and the substitution pattern (O2 ≥ O6) can be controlled by the NaOH concentration and increase to a certain extent with increasing amounts of NaOH (Heinze & Pfeiffer, 1999). The DS of carboxymethylation can also be increased by increasing the concentration of chloroacetic acid at a set NaOH concentration. For example, the maximum DS can be achieved at a molar ratio of cellulose: MCA = 1: 2.05 (Khullar et al., 2005). Regardless of the cellulose source and solvent system, reaction conditions of 55°C and 3 to 4 hours gave maximum DS at certain chemical concentrations (Khullar et al., 2005)(Heinze & Pfeiffer, 1999)(Heinze & Koschella, 2005)(Pushpamalar et al., 2006).

[0128]

[0129] Scheme 2: Carboxymethylation of cellulose fibers

[0130] The structural properties of cellulose are attributed to the fact that it can maintain a semi-crystalline aggregate state even in an aqueous environment, which is unusual for polysaccharides. In plant cells, it aggregates regularly along the chain, resulting in intermolecular and intramolecular hydrogen bonds and hydrophobic interactions, and forms a fiber structure called microfibril, which is composed of basic fibrils or nanofibrils, which are the basic structural units. Several cellulose sources have been used to obtain cellulose micro / nanofibers, including hardwood, softwood, soybean, cotton, wheat straw, bacterial cellulose, sisal, hemp, sugarcane bagasse, etc. Wood is the most important industrial source of cellulose fibers. However, it is a challenge to obtain microfibrillated cellulose from wood. Generally, a lot of energy is required to overcome the extensive and strong interfibril hydrogen bonds while maintaining intramolecular bonds. In other words, it is desirable to process the fibers in a manner that a micron / nanoscale diameter is obtained while maintaining a long axial length to obtain a high aspect ratio. In various microfibrillation processes, most are mechanical. For example, homogenization, microfluidization, the use of super grinders, grinding, fine grinding, freeze-crushing, etc. are all mechanical methods.

[0131] Typically, in the case of producing MFC via a simple mechanical method, high-intensity shearing forces are applied to cellulose pulp, resulting in individualization of fibrils. In these mechanical processes, homogenization is carried out under extremely high pressure and is characterized by using a relatively large amount of energy to fibrillate the fibers. During the homogenization process, the cellulose slurry passes through a very small gap between the homogenization valve and the impact ring, subjecting the fibers to shearing forces and impact forces, resulting in cellulose fibrillation. As an alternative to homogenization, microfluidization can be used to obtain micro / nano fibrils that are generally characterized by a diameter in the range of 20 to 100 nm and a length of tens of microns. Microfluidization includes passing a cellulose suspension through a thin chamber with a specific geometry (e.g., Z- or Y-shaped) and an orifice width of 100-400 microns under high pressure, wherein strong shearing forces and suspensions are impacted on the channel wall, resulting in cellulose fibrillation. Despite the production of high-quality MFC / NFC, in order to be economically viable, both processes face important challenges: the amount of energy used and operational issues such as clogging and industrial scalability.

[0132] Ultrafine friction grinding is another technology for producing MFC / NFC. The ultra-high mass colloid grinder of Masuko Sangyo Co.Ltd. in Japan is a commonly used example. MFC / CNF can be obtained by passing the natural fiber suspension "n" times through the grinding stone. The shear force generated by the grinding disc is applied to the fiber, which leads to the individualization of the cell wall stratification and thus the micro / nano fibrils. MFC / NFC is usually obtained with a diameter in the range of 20-90nm. Alternatively, MFC / NFC can also be produced using a disc or cone refiner by a process that includes both mechanical force and hydraulic force to change the fiber properties. Typically, pulp is pumped into the refiner and forced to pass between the rotating rods located on the stator and the rotor. Therefore, different types of stress (crushing, bending, pulling and pushing) are applied to the fiber between the refiner rods of the filler. Shear stresses such as rolling and torsion occur in the groove. Other mechanical processes such as ultrasonic treatment, low temperature crushing, ball milling, extrusion, aqueous counter collision (aqueous counter) and steaming and bursting can be used.

[0133] In some aspects, the subject matter disclosed at present relates to non-wood fiber, including fiber modification of non-wood fiber, characterization of non-wood fiber, generation of MFC by non-wood fiber pulp, and development of biocomposites for application in coating, film and composite materials by non-wood fiber to minimize the use of synthetic polymers. Among different non-wood biomass cellulose fiber sources, hemp and cocoa plants are more widely known for their uses in textile and chocolate industries, respectively. Industrial hemp (Cannabis Sativa L.) is the source of two types of fibers: bast fiber and woody stalk core. The bast fiber, which usually accounts for about 20 weight (wt) % to about 40 weight % of cellulose fiber in industrial hemp, is usually present in the outer layer of hemp stem, while the other about 60 weight % to about 80 weight % of industrial hemp fiber is hemp stalk core. (Thygesen et al., 2006) (Sareena et al., 2013). Hemp stalk core comes from the core part of hemp stem, and is mainly used for animal bedding and hemp crate construction materials. Cocoa pod husk (CPH) is an industrial byproduct of the chocolate industry, with millions of tons of cocoa pod husk discarded as waste material every year. Valorization of waste biomass can significantly promote the circular economy, reduce environmental pollution, and improve rural / farmer income and well-being.

[0134] As described below, fiber modifications, such as carboxymethylation and oxidation, are performed to enhance the swelling properties of non-wood derived cellulose fibers and to prepare biocomposites in combination with other cationic polymers for use in coatings, composite materials, and film development. CMC (partially or completely carboxymethylated cellulose) is hydrophilic in nature, and its water absorption properties can be customized by changing the DS. Due to the inherent hydrophilicity, once embedded on the surface, CMC mobility is limited. In addition, due to the presence of negative charges, CMC has an affinity for cationic polymers such as chitosan and cationic starch.

[0135]

[0136] Scheme 3: Periodate oxidation of hemp stalk core fibers

[0137] The polyhydroxy structure of cellulose makes it suitable for various oxidizing agents. For example, periodate oxidation of cellulose selectively destroys the ortho-hydroxyl groups at C2 and C3 in the anhydroglucose (AGU) unit of cellulose, thereby forming dialdehyde cellulose (DAC) (Coseri et al., 2013). See Scheme 3 above. The oxidation of the AGU unit of cellulose is carried out by forming a cyclic diester, followed by cleavage of the CC bond by a redox reaction and the final formation of DAC (Nevell, 1957). Due to the decomposition of the cellulose chain, DAC has a reduced crystallinity and a lower degree of polymerization. It also generates a higher amount of fine fibers, which may lead to lower energy consumption during conversion to MFC. Further oxidation of DAC leads to the formation of acid (Kim & Kuga, 2001), while reaction with amines by Schiff base reaction can introduce imine bonds between amines and cellulose (Wu & Kuga, 2006). According to one aspect of the subject matter currently disclosed, MFC generated by periodate oxidation of cellulose can form different composite materials that can replace and minimize the use of conventional plastic composite materials.

[0138]

[0139] Scheme 4: Periodate oxidation of carboxymethylated fibers

[0140] As described herein, periodate oxidation of CMC is performed to produce dicarboxymethylcellulose. See Scheme 4 above. Oxidation of CMC prior to mechanical treatment will significantly reduce energy consumption and promote nanofibrillation.

[0141] Therefore, as described herein, fiber modification of non-wood biomass, such as carboxymethylation, carboxymethylation followed by periodate oxidation, and periodate oxidation, will bring new functionality to the fiber and increase the level of fine fibers. The reduction in fiber length was confirmed by a fiber quality analyzer. Higher levels of primary and / or secondary fine fibers will reduce energy consumption during the production of MFC by mechanical treatment. MFC produced by CMC contains a higher number of anionic charges and carboxyl groups, thereby providing better adhesion to polymeric materials when developing biocomposites, while MFC produced by periodate oxidation and periodate oxidation of CMC will provide energy-efficient MFC production for the development of more hydrophobic composites.

[0142] In view of the low strength and relatively poor barrier properties of paper packaging materials, in some embodiments, the presently disclosed subject matter relates to the development of coatings and films based on the above-mentioned MFC to improve the overall performance of cellulose paper. Typically, MFC is composed of expanded bulk cellulose, which is moderately degraded and the surface area is greatly expanded. It can be obtained from the mechanical disintegration of the cellulosic material. MFC has a long and flexible structure and a large aspect ratio (length / diameter), with a length in the micrometer or millimeter range and a width in the nanometer range, but the aspect ratio of MFC can vary depending on the source of the cellulosic material, the type and duration of mechanical treatment (Agate et al., 2020). Currently, bleached wood pulp is considered to be the most common raw material for MFC production. However, industrial and agricultural biomass waste, such as straw, bagasse, carrot pulp, onion peels, and hemp stalk cores, can also be used to produce MFC. Among these materials, hemp is of interest because it is one of the strongest natural fibers. CPH is also of interest to the presently disclosed subject matter because it can account for up to 76% by weight of cocoa pods, but currently does not have significant market value.

[0143] Although have advantages, MFC may face the problem that its hydrophilicity is strong, and its strong hydrophilicity may hinder its use in composite material application and may cause aggregation due to hydrogen bond. MFC is also relatively inert usually, is not easy to carry out chemical operation. Another problem is that the generation of MFC can be a time-consuming and energy-consuming process. As described herein, pretreatment, such as chemical modification of hydroxyl group, can reduce energy consumption. As further described herein, other additives can be used to manufacture composite film based on MFC for coating purpose. These additives include for example chitosan, glycerol and cationic starch.

[0144] Chitosan is a partially deacetylated derivative of chitin, the second most abundant natural polysaccharide, and is a natural linear polysaccharide composed of 1,4-linked 2-amino-deoxy-β-d-glucans. It is reported to have strong antimicrobial and antifungal activities and has been used as a packaging material for food preservation (Jo et al., 2001)(Darmadji et al., 1994)(Kim et al., 2011)(No et al., 2007)(Khan et al., 2012).

[0145] Cationic starch is a favorable additive for use in the paper industry because it is renewable and environmentally friendly and has low cost. It is used in the paper industry because its positive charge is introduced to the starch molecule chain and the negative charge is introduced to the site on other fillers and can also have a strength-enhancing effect on paper (Gulsoy, 2014)(Hamzeh et al., 2013). However, cationic starch may also have some limitations, such as low tensile properties and high water vapor permeability. It may also have hydrophilic properties, making it difficult to control sensitivity to moisture content (Vaezi et al., 2019).

[0146] The brittleness and hydrophilic behavior of biopolymers mentioned above may affect the mechanical and barrier properties of food packaging. In some embodiments, these problems can be overcome by adding plasticizers such as glycerol. For different packaging applications, plasticized films can show greater flexibility and feasibility than unplasticized films. For example, as the concentration of glycerol increases, although the tensile strength decreases, the elongation at break can be improved (Tarique et al., 2021).

[0147] Thus, in some embodiments, the presently disclosed subject matter provides an evaluation of the mechanical and barrier properties of agricultural-based MFC composite films and coatings from hemp stalk cores and hemp blends (unmodified, carboxymethylated, and periodate-oxidized MFC) and from CPH (unmodified and modified), using other additives such as chitosan, cationic starch, and glycerol as a plasticizer. The effect of temperature in preparing film suspensions is described. Furthermore, in the case of CPH, the pulp itself has a fine fiber content of about 50% and a fiber length (Lw) of about 0.5 mm, which is close to MFC. Therefore, CPH is evaluated as a substitute for MFC without any mechanical treatment.

[0148] III. Packaging Materials Films and Coatings

[0149] In some embodiments, the presently disclosed subject matter provides a packaging material comprising a film (e.g., a stand-alone film) or a coating (e.g., a coating for a paper or paperboard material) comprising microfibrillated cellulose (MFC). In some embodiments, the MFC comprises or consists of an agro-based MFC (A-MFC), i.e., an MFC derived from pulp comprising or consisting of a non-wood lignocellulosic feedstock. In some embodiments, the film or coating has (i.e., exhibits) less than about 5% and / or less than about 2.5 g / m 2 when contacted with hot oil (i.e., oil heated to 65° C.) for 20 minutes. 2 of weight increase.

[0150] In some embodiments, the A-MFC is derived from pulp having a primary fines level greater than about 10%. In some embodiments, the pulp has a primary fines level greater than about 15%, greater than about 20%, greater than about 25%, greater than about 30%, greater than about 35%, greater than about 40%, or greater than about 45%. In some embodiments, the pulp has a primary fines level of about 15% to about 50% and / or an average fiber length of about 0.4 millimeters (mm) to about 0.6 mm (i.e., about 0.40, 0.42, 0.44, 0.46, 0.48, 0.50, 0.52, 0.54, 0.56, 0.58, or about 0.60 mm).

[0151] The non-wood lignocellulosic raw material can be any suitable non-wood lignocellulosic raw material. In some embodiments, the A-MFC is derived in whole or in part from waste biomass raw materials. For example, in some embodiments, the non-wood lignocellulosic raw material can be agricultural residues or other waste products (e.g., crop residues, such as wheat straw or rice straw or corn stalks) or industrial waste or by-products derived from agricultural products (e.g., lignocellulosic material by-products produced during the processing of plant materials such as hemp stalk cores, cocoa pod shells or bagasse (i.e., sugar cane and / or sorghum bagasse). Therefore, in some embodiments, the packaging material currently disclosed includes a film or coating made of alternative (i.e., non-wood) fibers and can combine recyclability, biodegradability and sustainability.

[0152] In some embodiments, non-wood lignocellulosic raw materials comprise a mixture of different non-wood lignocellulosic raw materials. In some embodiments, non-wood lignocellulosic raw materials can be mixed with wood-based raw materials (i.e., hardwood or softwood raw materials). In some embodiments, at least about 50% (by weight) of MFC in film or coating is derived from pulp from one or more discarded biomass raw materials. In some embodiments, at least about 60% or at least about 70% of MFC is derived from pulp from discarded biomass. In some embodiments, about 70% to about 100% (for example, about 70%, about 72%, about 74%, about 76%, about 78%, about 80%, about 82%, about 84%, about 86%, about 88%, about 90%, about 92%, about 94%, about 96%, about 98% or about 99%) of MFC is derived from pulp derived from discarded biomass. In some embodiments, all MFCs are derived from discarded biomass (i.e., packaging material does not contain any wood-derived papermaking fibers). In some embodiments, the non-wood lignocellulosic feedstock comprises or consists of hemp stalk cores, a mixture of hemp stalk cores and hemp bast, bagasse, cocoa pod husks, and combinations thereof.

[0153] Pulp for preparing MFC can be derived from raw materials via any suitable pulping method, which can decompose biomass raw materials to provide discrete fibers that can be dispersed in aqueous solution. In particular, due to the fineness of the raw materials, the core fibers of hemp stalk cores and other hemp wastes are relatively easy to penetrate, which can make it possible to use a variety of methods for pulping (Santos et al., 2013). In some embodiments, the pulping method is selected to provide fibers at a desired yield and / or to provide fibers with one or more desired properties, for example, desired lignin content, length, freeness, brightness, kappa number, etc. In some embodiments, pulping is carried out by a chemical pulping method, such as kraft pulping, sulfite pulping, soda pulping or carbonate pulping. Kraft pulping, which accounts for about 80% of pulping in the paper industry, includes digesting a cellulosic raw material or a lignocellulosic raw material in an aqueous dispersion containing sodium hydroxide and sodium sulfide, usually at elevated temperatures and / or pressures (Gustafson et al., 1983). Carbonate (Na2CO3) and soda (NaOH, KOH or Ca(OH)2) pulping can be carried out at ambient temperature (e.g., about 18°C ​​to about 25°C) or at elevated temperatures (Zhang et al., 2011)(Brodeur et al., 2019)(Yamashita et al., 2010). When carried out at elevated temperatures, pulping time can be reduced. In addition, autohydrolysis using chemical-free or substantially chemical-free hot water treatment can be used. In some embodiments, autohydrolysis can be carried out under alkaline conditions (e.g., to remove pectin). In some embodiments, pulping can be carried out using enzymes (e.g., cellulases). In addition to kraft pulping, these pulping technologies provide reduced or no sulfur dioxide and odor gas emissions due to the use of sulfur-free chemicals.

[0154] Therefore, in some embodiments, pulp comprises kraft fiber, soda fiber (also referred to herein as "alkali fiber") and / or self-hydrolyzing fiber. In some embodiments, pulp comprises high-yield pulp or pulp containing high amounts of lignin. For example, pulp containing high amounts of lignin can be pulp containing more than about 5% lignin, more than about 10% lignin, or more than about 15% lignin. In some embodiments, lignin containing high amounts of lignin can contain up to about the same relative amount of lignin as that present in the raw material for preparing pulp. In some embodiments, pulp comprises fibers all produced by the same pulping process. However, since pulping processes can impart different properties in papermaking fibers, even in fibers derived from the same raw materials, in some embodiments, papermaking fibers include a mixture of fibers produced by more than one type of pulping process (e.g., a combination of kraft fibers and alkali / soda fibers or a combination of kraft fibers and self-hydrolyzing fibers).

[0155] In some embodiments, kraft pulping or soda pulping of waste biomass can be performed using reduced amounts of chemicals compared to the amounts of chemicals typically used in the paper industry, thereby producing a relatively more sustainable and / or environmentally friendly pulp. For example, in some embodiments, kraft fibers are pulped using a pulping / cooking mixture that contains less than the typical 18% active alkali. In some embodiments, kraft fibers are pulped using a pulping / cooking mixture that contains about 12% active alkali. In some embodiments, alkali / sodium pulping includes a pulping / cooking mixture that contains about 8% alkali hydroxide (e.g., about 8% NaOH).

[0156] Depending on the desired end use of, for example, packaging materials, in some embodiments, at least a portion of the pulp used to prepare the MFC may include bleached and / or refined fibers. As with pulping, in some embodiments, bleaching can be carried out using less than the typical amount of chemicals currently used in the paper industry. In some embodiments, bleaching can be carried out using an ECF process involving three steps rather than more typical five steps, or only using peroxide. In some embodiments, only peroxide bleaching produces a more natural color pulp, which can produce a more natural color packaging product. In some embodiments, the fiber can be bleached to provide a brighter appearance and / or an appearance more similar to bleached wood-based paper. In some embodiments, the International Organization for Standardization (ISO) brightness of the fiber is at least about 80 (e.g., at least 80, 81, 82, 83, 84 or about 85). In some embodiments, the ISO brightness of papermaking fibers is about 80 to about 85.

[0157] MFC (e.g., A-MFC) can be chemically modified or unmodified. For example, in some embodiments, A-MFC comprises or consists of modified A-MFC, wherein the modified A-MFC comprises MFC derived from chemically modified pulp. Chemical modification may involve one or more hydrophobization, grafting, or oxidation reactions known in the paper and / or pulping industry. In some embodiments, the modification comprises carboxymethylation, oxidation, or a combination thereof. Thus, in some embodiments, the modified A-MFC comprises or consists of carboxymethylated A-MFC; oxidized A-MFC; carboxymethylated and oxidized A-MFC, or a combination thereof (e.g., it may contain A-MFC from two different pulps, one carboxymethylated and one oxidized or one carboxymethylated and one carboxymethylated and oxidized). In some embodiments, the oxidized A-MFC comprises periodate-oxidized A-MFC. In some embodiments, the oxidized A-MFC comprises dialdehyde cellulose.

[0158] In some embodiments, the film or coating prepared from MFC comprises from about 5 weight percent (wt %) to about 90 wt % A-MFC (e.g., about 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, or 90 wt % A-MFC). In some embodiments, the film or coating comprises from about 40 wt % A-MFC to about 80 wt % A-MFC (e.g., 40, 42, 44, 46, 48, 50, 52, 54, 56, 58, or about 60 wt % A-MFC).

[0159] In some embodiments, film or coating also comprises one or more additives, for example, one or more additives known in the field of papermaking, such as but not limited to sizing agent, adhesive, filler, wet and / or dry strength agent, retention and drainage aid, optical brightener (for example, stilbene or other fluorescent compounds), plasticizer, crosslinking agent, surface sizing agent, biocide and dye or other coloring agent. For example, sizing agent can include alkyl ketene dimer (AKD), rosin and rosin derivatives and alkenyl succinic anhydride. Adhesive includes but is not limited to cation and anion hydroxyethyl cellulose (EHEC), modified starch (for example, cationic starch), dextrin and styrene copolymer, such as styrene maleic anhydride copolymer and styrene-acrylate copolymer. Fillers commonly used in papermaking include but are not limited to calcium carbonate, titanium dioxide, dolomite, clay and talc. Strength agents include, for example, starches such as oxidized starch, ethylated starch, enzyme-treated starch, and cationic starch (e.g., starch modified with quaternary ammonium cations such as 2,3-epoxypropyltrimethylammonium chloride or 3-chloro-2-hydroxypropyltrimethylammonium chloride), sodium alginate, guar gum, protein, soy lecithin, dextrin, and polyacrylamide. Retention and drainage aids include, but are not limited to, calcium carbonate and polyethyleneimine. Crosslinking agents include, but are not limited to, polycarboxylic acids such as acrylic acid, maleic acid, polymaleic acid, succinic acid, polyitaconic acid, and citric acid. Plasticizers include bio-based plasticizers (e.g., citrates, such as triethyl citrate (TEC), acetyl triethyl citrate (ATEC), acetyl triethyl citrate (ATEC), tributyl citrate (TBC), acetyl tributyl citrate (ATBC), trioctyl citrate (TOC), butyryl trihexyl citrate (BTHC), trihexyl trihexyl citrate and trimethyl citrate (TMC)), dicarboxylate / tricarboxylate-based plasticizers, adipate-based plasticizers, sebacic acid-based plasticizers and / or maleate-based plasticizers, as well as glycerol, triacetin, tributyl citrate, polyethylene glycol, etc. In some embodiments, additives may include polyhydroxyalkanoates (PHA), such as, but not limited to, poly-3-hydroxyvalerate (PHV) or poly-4-hydroxybutyrate (P4HB). Representative amounts of such additives may be, for example, in the range of about 0.5% to about 30% by weight of the film or coating. In some embodiments, film or coating comprises one or more of chitosan, cationic starch, glycerol, triethyl citrate, PHA and AKD. In some embodiments, film or coating can comprise about 15 wt % to about 25 wt % chitosan (for example, about 15, 20 or 25 wt % chitosan). In some embodiments, film or coating can comprise about 15 wt % to about 25 wt % cationic starch (for example, about 15, 20 or about 25 wt % cationic starch). In some embodiments, film or coating comprises about 0.5 wt % to about 5 wt % glycerol (for example, about 0.5, 1, 2, 3, 4 or 5 wt % glycerol).In some embodiments, the film or coating comprises about 0.5 wt % to about 5 wt % AKD (eg, about 0.5, 1, 2, 3, 4, or 5 wt % AKD).

[0160] As described above, in some embodiments, the pulp used to prepare the MFC has a primary fines level (or primary and / or secondary fines level) of more than 10% (e.g., about 15%, 20%, 25%, 30%, 35%, 40%, 45%, or about 50%). In some embodiments, chemical modification and / or fibrillation can increase the fines level and / or reduce the average fiber length. Thus, in some embodiments, the MFC (e.g., A-MFC) has a total fines level (e.g., a combination of primary and secondary fines) of about 50% to about 95% (e.g., about 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, or about 95% fines). In some embodiments, the MFC (e.g., A-MFC) has an average fiber length of about 0.1 mm to about 0.45 mm (e.g., about 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, or about 0.45 mm).

[0161] The film and coating of the currently disclosed theme can have any desired thickness. In some embodiments, the film or coating can have a thickness of about 1 micron (mm) to about 200mm (e.g., about 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190 or about 200mm). In some embodiments, the currently disclosed coating has a thickness of about 1mm to about 30mm. In some embodiments, the currently disclosed film has a thickness of about 10mm to about 200mm. In some embodiments, the film or coating has a thickness of about 20mm to about 140mm. In some embodiments, the film or coating has a thickness of about 0.5 cubic centimeters per gram (cm 3 / g) to about 3.5cm 3 / g to about 2.0cm 3 / g of bulk volume. In some embodiments, the film or coating has a bulk volume of about 0.5 cm 3 / g to about 2.0cm 3 / g (e.g., about 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or about 2.0 cm 3 / g) of bulk volume.

[0162] The films or coatings of the presently disclosed subject matter can have one or more desirable barrier properties (e.g., for use in food and / or beverage packaging). In some embodiments, the films or coatings have a desired level of resistance to oil, water vapor, or other gases. For example, as described above, in some embodiments, when contacted with hot oil (i.e., oil heated to 65° C.) for 20 minutes, the films or coatings have (i.e., exhibit) less than about 5% and / or less than about 2.5 g / m 2 In some embodiments, the film or coating has a weight gain of less than about 2% (e.g., less than about 2.0%, 1.9%, 1.8%, 1.7%, 1.6%, 1.5%, 1.4%, 1.3%, 1.2%, 1.1%, or about 1%) when contacted with hot oil for 20 minutes. In some embodiments, the film or coating has a weight gain of less than about 1.19 g / m 2 (e.g., less than about 1.19, 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, 1.2, 1.1, 1.0, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, or about 0.1 g / m 2 ). In some embodiments, the film or coating has a weight gain of less than about 3% when in contact with room temperature oil for 15 hours. In some embodiments, the film or coating has a weight gain of about 1% to about 2.5% (e.g., about 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, or about 2.5%) when in contact with room temperature oil for 15 hours. In some embodiments, the film or coating has a weight gain of less than about 1.8 g / m 2 In some embodiments, the film or coating has a weight gain of less than 50 g / m2 mm / day (g / m 2 .mm / day). In some embodiments, the film or coating has a water vapor transmission rate (WVTR) of less than about 45 g / m 2 .mm / day, less than about 40g / m 2 .mm / day, less than about 35g / m 2 .mm / day, less than about 30g / m 2 .mm / day, less than about 25g / m2 .mm / day, less than about 20g / m 2 .mm / day or less than 15g / m 2 .mm / day WVTR. In some embodiments, the film or coating has a WVTR of about 0.3 g / cm3 (g / cm 3 ) to about 2.1 g / cm 3 (e.g., about 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, or about 2.1 g / cm 3 ) density. A film with a lower WVTR can be prepared by preparing a film with a higher density.

[0163] In some embodiments, film or coating can have one or more desired mechanical properties. In some embodiments, film or coating have about 30 Newton meters / gram (Nm / g) or larger tensile index. In some embodiments, tensile index is about 30Nm / g to about 300Nm / g (for example, about 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290 or about 300Nm / g). In some embodiments, film or coating have about 1.5% or higher tensile rate. In some embodiments, the film or coating has a stretchability of about 1.5% to about 10% (e.g., about 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, or about 10%). In some embodiments, the film or coating has a stretchability of about 3% to about 8% or about 4% to about 8%.

[0164] The films and coatings of the presently disclosed subject matter can be used for any packaging material, for example, for packaging materials that may need to provide a barrier to oil, water or gas, as well as packaging materials that are interested in more sustainable and / or biodegradable materials. Thus, the packaging material can be used for food and / or beverage packaging, pharmaceutical packaging, electronic equipment packaging, personal care and / or cosmetic packaging, and / or for packaging of disposable items (disposable utensils, certain medical supplies such as disposable syringes, etc.).

[0165] In some embodiments, the packaging material is a food or beverage packaging material. Therefore, for example, the packaging material can be a food packaging, which includes or consists of a film of the currently disclosed theme, or a food or beverage packaging material (on a surface intended to be in contact with food or beverage, on a surface intended to be in contact with an external environment (e.g., air) or on both such surfaces) coated with a coating or film of the currently disclosed theme. Therefore, in some embodiments, the packaging material includes a substrate, wherein the substrate is coated with a film or coating comprising A-MFC on at least one surface. In some embodiments, the substrate is a flexible substrate. In some embodiments, the substrate includes paper or other biodegradable and / or sustainable materials. In some embodiments, paper or other substrates include or consist of fibers (e.g., papermaking fibers) derived from waste biomass. Therefore, in some embodiments, the packaging material can include more than 50%, 60%, 70%, 80%, 90%, 95% or more sustainable and / or recyclable materials, such as materials derived from waste biomass. In some embodiments, the packaging material includes 100% biodegradable and / or recyclable materials.

[0166] Food packaging material can provide in any desired form, for example, as the coated sheet (for example, butcher paper) for wrapping food articles or as the coated bag or other containers for food, for example, box, carton, tray, plate, bowl, cup, lid, take-away container, flip-top container for cup or other containers.In some embodiments, food packaging material can be the packaging material for human food.In some embodiments, food packaging material can be used as the flexible flow packaging (flowwrap) for sugar products such as but not limited to chocolate candy bar, chewing gum, mint, fruit-flavored candy and sugar-coated candy.In some embodiments, food packaging material can be the packaging material for the food of pet or other animals (for example, the animal in farm or zoo), as the packaging material for pet food.In some embodiments, food packaging material can be used for providing at least one assembly of food packaging articles, and described at least one assembly also comprises one or more other materials (for example, plastic or metal foil assembly).

[0167] In some embodiments, the presently disclosed subject matter provides for preparing a membrane comprising A-MFC (i.e., having a viscosity less than about 5% and / or less than about 2.5 g / m2 when contacted with hot oil (i.e., oil heated to 65° C.) for 20 minutes. 2In some embodiments, the method comprises: (a) preparing a suspension comprising A-MFC (i.e., wherein the A-MFC is MFC prepared from pulp from a non-wood lignocellulosic feedstock, optionally wherein the pulp has a primary fines level greater than about 10% or wherein the pulp has a high level (e.g., greater than about 40%, 45%, or 50%) of primary and / or secondary fines); (b) forming a web using the suspension; and (c) drying the web to provide a film.

[0168] A-MFC can be an MFC from any suitable non-wood lignocellulosic feedstock as described above. Thus, in some embodiments, the non-wood lignocellulosic feedstock comprises one or more agricultural residues and / or industrial byproducts. In some embodiments, the non-wood lignocellulosic feedstock comprises hemp stalk core, a mixture of hemp stalk core and hemp bast, cocoa pod shells, or a combination thereof.

[0169] In some embodiments, preparing a suspension comprising A-MFC comprises fibrillating a suspension of pulp from a non-wood lignocellulosic feedstock, wherein the pulp has a primary fines level of more than 10%. In some embodiments, the pulp has a primary fines level of about 15% to about 50% (e.g., about 15%, 20%, 25%, 30%, 35%, 40%, 45%, or about 50%).

[0170] Pulp can be pulped by any suitable means, and can be bleached or unbleached. In some embodiments, pulp is kraft pulp, autohydrolysis pulp, unbleached pulp, higher yield pulp and / or pulp containing higher lignin. In some embodiments, some or all of the pulps are chemically modified (e.g., carboxymethylated) before or after fibrillation. In some embodiments, some or all of the pulps are chemically modified before fibrillation. In some embodiments, chemical modification can include carboxymethylated pulp, oxidized pulp or carboxymethylated and oxidized pulp. In some embodiments, oxidation is periodate oxidation. Chemical modification can increase the total level of fine fibers in the pulp before fibrillation. In some embodiments, chemical modification can reduce the amount of energy used in making pulp fibrillation. In some embodiments, increasing the degree of substitution of modified pulp (i.e., the average DS of modified fibers in pulp) can reduce the amount of energy used in making pulp fibrillation. In some embodiments, DS is less than about 1.2. In some embodiments, DS is from about 0.8 to about 1.2. In some embodiments, the use of pulp derived from or at least partially derived from CPH can reduce the amount of energy used in fibrillating the pulp. In some embodiments, the amount of energy used to fibrillate the fibers is less than about 5000 kilowatt-hours / ton (KWH / T). In some embodiments, the energy used to fibrillate the fibers is less than about 4500 KWH / T, less than about 4000 KWH / T, less than about 3500 KWH / T, less than about 3000 KWH / T, less than about 2500 KWH / T, less than about 2000 KWH / T, less than about 1500 KWH / T, or less than about 1000 KWH / T.

[0171] Carboxymethylation can be carried out in an aqueous medium, rather than using a traditional organic solvent. For example, carboxymethylation can be carried out by preparing a fiber slurry (e.g., about 4% fiber) and a carboxymethylating agent such as haloacetic acid (e.g., chloroacetic acid or its salt) and stirring the reaction mixture for several hours (e.g., about 4 hours) at an elevated temperature (e.g., about 60°C) (Chang et al., 2010). An aqueous solution of an alkali (e.g., NaOH or KOH) can be added and the resulting mixture can be kept for a period of time (8 to 14 hours) at a suitable temperature (e.g., room temperature to about 70°C). The carboxymethylated fiber can then be separated and washed with ethanol and / or water. The amount of the carboxymethylating agent used can be between about 0.5 moles to about 20 moles per anhydrous glucose residue in the fiber. Using a higher amount of carboxymethylating agent can achieve a higher substitution level (higher DS). Periodate oxidation can be carried out, for example, by preparing a 4% fiber slurry with sodium periodate (NaIO4). (Chang et al., 2010). The reaction mixture can be heated (eg, to about 55° C.) and shaken or stirred for a period of time (eg, about 2 hours).

[0172] In some embodiments, preparing a suspension comprising A-MFC includes contacting A-MFC with a liquid to provide a suspension comprising a total solid content (i.e., total dry component content) of A-MFC comprising at least about 50 weight percent (wt%). In some embodiments, the liquid is water. In some embodiments, the total solid content comprises about 50 wt% to about 80 wt% A-MFC (i.e., about 50 wt% to about 80 wt% of the solids in the suspension, i.e., 50%, 55%, 60%, 65%, 70%, 75% or about 80% is A-MFC). In some embodiments, the suspension as a whole comprises a solid content of about 5% or less. In some embodiments, the suspension as a whole comprises a solid content of about 2.0% or more. In some embodiments, the solid content is between about 2.0% to about 2.5% of the suspension.

[0173] In addition to A-MFC, the solid in the suspension can also include one or more additives. Therefore, in some embodiments, the suspension also includes one or more of chitosan, cationic starch, glycerol, triethyl citrate, PHA and AKD. For example, in some embodiments, the solid content includes about 15% by weight to about 25% by weight of chitosan or cationic starch (for example, about 20% by weight of chitosan or about 20% by weight of cationic starch). In some embodiments, the solid content includes about 1% by weight to about 5% by weight of glycerol. In some embodiments, the solid content includes about 1% by weight to about 5% by weight of AKD.

[0174] In some embodiments, the temperature used when preparing the suspension may affect the properties of the film or coating prepared by the suspension. In some embodiments, preparing the suspension includes mixing the suspension (e.g., stirring or shaking the suspension) for a period of time at a temperature between about room temperature and about 80°C. In some embodiments, the temperature is about 18°C ​​to about 25°C. In some embodiments, the temperature is about 30°C, about 35°C, about 40°C, about 45°C, about 50°C, about 55°C, about 60°C, about 65°C, about 70°C, about 75°C or about 80°C. In some embodiments, the temperature is about 80°C. In some embodiments, mixing is carried out for about 15 minutes to about 2 hours (e.g., 15, 30, 45, 60, 75, 90, 105 or about 120 minutes). In some embodiments, mixing is carried out for about 30 minutes.

[0175] In some embodiments, step (b) includes cast web or applies suspension to the surface of substrate. In some embodiments, step (b) includes cast web, drying web (for example, in air or oven) to form film and then web is applied to the surface of substrate to provide coated substrate. In some embodiments, substrate is paper substrate or other materials made of biodegradable and / or sustainable materials. In some embodiments, method also includes forming packaging material by film or by coated substrate. Forming packaging material can include one or more of the conversion technologies used in packaging, such as calendering, coating, printing, embossing, slitting, sheeting, folding, crease, wrapping, gluing (sealing), lamination, etc. For all mentioned conversion technologies, several methods are known. For example, in some embodiments, calendering can include super calender, hard nip calender (hardnip calender) or hot soft nip calender (hotsoft nip calender). In some embodiments, printing method can include but is not limited to flexographic printing, rotary gravure printing, offset lithography, inkjet printing or electrophotographic printing, etc. In some embodiments, the sealing operation may involve the use of a cold sealant or a hot sealant. In some embodiments, the wrapping operation may include the use of a horizontal form fill sealer (HFFS) or a vertical form fill sealer (VFFS), depending on the wrapping requirements.

[0176] In some embodiments, packaging materials of the presently disclosed subject matter can have the same or similar appearance and / or feel as packaging materials made from conventional packaging materials and / or wood-based paper packaging materials.

[0177] Example

[0178] The following examples are included to further illustrate various embodiments of the presently disclosed subject matter. However, in light of the present disclosure, those of ordinary skill in the art will appreciate that many changes may be made to the specific embodiments disclosed and still obtain the same or similar results without departing from the spirit and scope of the presently disclosed subject matter.

[0179] Example 1

[0180] Chemical modification

[0181] Material:

[0182] Bleached hemp stalk core (from the Netherlands) and cocoa pod shell (from South America) were processed by disc refining, while hemp mixture (from the United States) was refined by Valley pulping. Southern bleached hardwood and softwood were used after refining. All chemicals used in fiber modification (0.68M and 1.03M sodium chloroacetate (CMA), 1.25M NaOH, alcohol reagent, 0.16M NaIO4) and characterization (0.1M NaOH, 0.1M HCl, 70% methanol, NH2OH.HCl, ethylenediamine copper (II) double hydroxide) were obtained from Fisher Scientific (Hampton, New Hampshire, USA) and used as is.

[0183] All chemical modification reactions were performed using unrefined hemp stalk core, hemp blend (Valley pulp), cocoa pod shells, and refined hardwood (2500 PFI refinement). For simplicity, the following sample IDs were used herein: HH-NL (hemp stalk core, Netherlands), HM-US (hemp blend, United States), CPH (cocoa pod shells), HW (hardwood), SW (softwood), CM (carboxymethylation), PI (periodate oxidation), CMPI (carboxymethylation followed by periodate oxidation), MFC (microfibrillated cellulose), CM-HH-MFC (microfibrillated carboxymethyl hemp stalk core), CM-HM-MFC (microfibrillated carboxymethyl hemp blend), CM-HW-MFC (microfibrillated carboxymethyl hardwood), CMPI-HH-MFC (microfibrillated carboxymethyl-periodate oxidation hemp stalk core), and PI-HH-MFC (microfibrillated periodate oxidation hemp stalk core).

[0184] Carboxymethylation to produce carboxymethyl cellulose (CMC)

[0185] Carboxymethylation of hemp stalk core, hemp mixture, cocoa pod shell and hardwood fibers was performed using a modified method based on the method previously described in the literature (Sim, 2015) using green solvent as the reaction medium. Similar reaction conditions were maintained for all fibers to compare the results of modified fibers and biocomposites made from modified fibers, MFC and corresponding biopolymers. A 4% fiber slurry with 0.68M CMA was prepared using deionized (DI) water as the green solvent. The reaction was carried out at 60°C for 4 hours in a mechanical shaker. After 4 hours, 100mL of 1.5M NaOH solution was added to the pulp slurry and the flask containing the pulp was left overnight at room temperature. The next day, the slurry was washed with 70% ethanol and then with DI water to remove unreacted CMA and any contaminants in the modified fibers. A second batch of hemp stalk core was carboxymethylated using a higher concentration of CMC (1.05M) while keeping all other conditions similar to prepare carboxymethylated hemp stalk core fibers with a higher degree of substitution (DS).

[0186] Periodate oxidation to prepare dialdehyde cellulose (DAC)

[0187] Periodate oxidation of wood and non-wood fibers was performed based on a method previously described in the literature (Chinga-Carrasco and Syverud, 2014) and was updated according to laboratory requirements. 50.0 g OD mass (oven dried) of hemp stalk core fiber was suspended in DI water with a concentration of 4% cellulose and 0.16 M NaIO4 in a 2 L flask. The flask was covered with aluminum foil to prevent photoinduced decomposition of periodate and the reaction was carried out at 55 °C in a mechanical shaker for 2 hours. After 2 hours, the product was filtered and washed several times with DI water to remove iodine-containing compounds and unreacted reagents.

[0188] Carboxymethylation followed by periodate oxidation (CMPI)

[0189] The fiber is subjected to this modification to produce carboxymethylated dialdehyde cellulose. First, the fiber is carboxymethylated as described above, and then the carboxymethylated fiber is further reacted with NaIO4 to produce carboxymethylated dialdehyde cellulose.

[0190] A summary of the different fiber modifications and the conditions used for the modifications is shown in Table 1 below.

[0191] Table 1: Different types of fiber modification and their conditions

[0192]

[0193] Example 2

[0194] Preparation of Microfibrillated Cellulose (MFC)

[0195] MFC was prepared from modified and unmodified hemp, cocoa pod shells and hardwood fibers using a top-down method (Chauhan & Chakrabarti, 2012). A suspension of 3 wt% HH, HM, CPH, HW, CM-HH, CM-HM, CM-HW and 4 wt% PI-HH and CMPI-HH was prepared using a Lightning mixer and mixed for 15 minutes to obtain a consistent fiber suspension. The pulp suspension was then passed through a Masuko Super Mass collider (Masuko Sangyo Co. Ltd., Japan) equipped with a silica grinding stone (E6-46DD) at a speed of 2400 rpm for further fibrillation. See Figure 1The gap between the upper and lower grinders was kept negative while the pulp was passing through. The samples were collected after fibrillation at different cumulative energies. Three MFC samples were taken from each pulp suspension and dried using an IR solids analyzer to obtain the solids content and averaged to obtain the average solids content value.

[0196] Example 3

[0197] Fiber, modified fiber and MFC characterization

[0198] Fourier Transform Infrared Spectroscopy (FTIR):

[0199] Using PerkinElmer SPECTRUM TM FTIR spectra of modified and unmodified fibers were recorded using a spectrometer (PerkinElmer Corporation, Waltham, MA, USA). Each sample was placed in an attenuated total reflectance (ATR) diamond crystal with a contact area of ​​1.5 mm diameter circle. Oven-dried samples were placed in contact with the area to be analyzed. All spectra were obtained between 4000 and 500 cm -1 Each sample was scanned 20 times with a resolution of 4 cm -1 To compare the data, a baseline correction was performed and all spectra were collected at the same baseline.

[0200] Microscopy:

[0201] The morphology of unmodified and modified MFCs was characterized using a Hitachi S-3200N variable pressure scanning electron microscope (VPSEM; Hitachi, Tokyo, Japan). Each sample was sputter-coated with AuPd for 5 minutes and then visualized at 2 kV under the same magnification. SEM images were taken at three different magnifications: 500 times (500x), 1000 times (1000x) and 5000 times (5000x). Transmission electron microscope (TEM) images of each sample were also taken at a magnification of 5000x.

[0202] Determination of degree of substitution (DS) of carboxymethylation:

[0203] The degree of substitution (DS) of carboxymethylation of hemp stalk core, hemp mixture and hardwood fiber was measured according to the modified Na Wu method (Wu et al., 2018). According to this method, 1.0 g of oven-dried carboxymethylated cellulose sample was placed in a 250.0 mL conical flask. Then, 8.0 mL of 70.0% methanol was added to the flask and allowed to stand for 2-3 minutes. After 2-3 minutes, 100 mL of deionized water was added and stirred with a magnetic stirrer for 2 hours. Two drops of methyl orange were added and the mixture was titrated with 0.1 N HCl solution. DS was calculated according to the following formula:

[0204]

[0205] Wherein, 0.162 is the molar mass of the anhydroglucose unit, g / mmol; 0.058 is the net increase in the mass of AGU per substituted carboxymethyl group, g / mmol; X is the carboxyl content per gram of sample, mmol / g; N is the total carboxyl content of the sample, mmol; and m is the absolute dry mass of the sample, g.

[0206] Fiber Quality Analysis (FQA):

[0207] A high-resolution fiber quality analyzer (HiRes FQA, OpTest Equipment Inc, Hawkesbury, Ontario, Canada) was used to measure the fiber length (l w ), fine fiber level and other physical properties. Before running the equipment, the FQAs were calibrated according to the manufacturer's guidelines and the fibers were disintegrated using a laboratory disintegrator. FQAs of unmodified, modified and microfibrillated cellulose (MFC) were determined.

[0208] Degree of Polymerization (DP):

[0209] According to the standard viscosity determination method (CM-15:88,1998) (Moutou et al., 2004), a glass capillary viscometer (Schott and Gen, Mainz, Germany) and fresh CED solvent (Carlo Erba Reagents Srl, Milan, Italy) are used to determine the average degree of polymerization (average DPv) of modified and unmodified MFC. Twenty-five milligrams of oven-dried MFC samples are dissolved in 50 mL of a solution consisting of 25 mL of copper (II) (CED) and 25 mL of deionized water. The effluent time of the solution is measured in duplicate. The Mark–Houwink–Sakurada equation is used to calculate the average DPv (Evans & Wallis, 1989).

[0210] Charge measurement:

[0211] The total charge content on the fiber surface was measured using a colloidal titration method (Tyagi et al., 2019). Polyelectrolyte titration was performed to determine the sign and magnitude of the ionic charge present on the fiber surface, and the endpoint was determined using a streaming amperometry method. To determine the net charge, both unbleached and bleached fiber samples were disintegrated into pulp at a solids concentration of 0.075% in deionized water. The colloidal charge of 200 ml of pulp suspension was evaluated by titration using a Chemtrac ECA 2000P streaming amperometry (Chemtrac Inc., Norcross, GA, USA). The endpoint of fiber charge neutralization was determined by the addition of a cationic polymer, poly(diallyldimethylammonium chloride) (polyDADMAC).

[0212] Total carboxyl content analysis:

[0213] The total carboxyl content of different fibers was measured by an acid-base titration method (Ghorpade et al., 2017)(Mali et al., 2018). Briefly, 100 mg of oven-dried pulp was dissolved in 20 mL of 0.1 N NaOH and stirred with a magnetic stirrer for 2 h. The excess 0.1 N NaOH was titrated with 0.1 N HCl using phenolphthalein as an indicator. The total carboxyl content per 100 g of pulp slurry was calculated in milliequivalents based on the following formula:

[0214] Carboxyl content = (V b -V a )x N x 100 / W

[0215] Among them, V b and V a are the volumes of HCl in the absence and presence of pulp samples, respectively; N is the normality of HCl; W is the weight of the sample (g).

[0216] Example 4

[0217] Discussion of Examples 1-3

[0218] Various techniques have been used to analyze the physical, chemical and morphological characteristics of chemically modified fibers. For example, as a part of the development of biocomposite materials in advanced applications for coating and film development, the modification of non-wood fibers (for example, hemp stalk core, hemp mixture and cocoa pod shell fibers) and the generation of MFC under different energy consumptions have been studied. Energy consumption, fine fiber level, charge analysis, carboxyl content and degree of substitution under different modification steps and after MFC production have been studied. The modification of hardwood (HW) fibers and the production of MFC have also been studied to provide reference samples to compare wood fibers and non-wood biomass in composite material development.

[0219] FTIR analysis:

[0220] Figure 2A and 2B FTIR spectra of modified and unmodified fibers are shown. -1 The stretching that occurs in the region is believed to be due to the presence of COC vibrations of the primary and secondary hydroxyl groups of the carbohydrates ( et al., 2009). At 1281, 1370 and 1427 cm -1 The peak at is believed to be mainly attributed to the presence of aromatic esters, ethers and phenolic compounds (Tanpichai et al., 2019).

[0221] 1650cm in PI, CMPI and CM modified cellulose -1 The peak at 2900cm indicates the presence of C=O stretching of carboxyl and keto groups (Pelissari et al., 2014). There are sharp peaks in periodate and carboxymethylated-periodate oxidized fibers due to the presence of DAC, while relatively weak stretching is present in carboxymethylated fibers due to the presence of C=O groups in CMC modified fibers. This stretching vibration is absent in unmodified fibers, indicating that carboxymethyl groups and dialdehyde functional groups were successfully introduced into the modified fibers. Hemp stalk core (HH), hemp mixture (HM) and hardwood (HW) all show similar stretching vibration trends. Corresponding to 2900cm -1 The peaks at 3400 cm are attributed to symmetric and asymmetric CH stretching, while the peaks at 3400 cm -1 The peak at is characteristic of the OH stretching of cellulose (Tanpichai et al., 2019).

[0222] Degree of substitution (DS) of carboxymethylation:

[0223] The DS of carboxymethyl cellulose directly affects the viscosity, emulsification, stability, solubility, stability, acid resistance and energy consumption of MFC produced from carboxymethylated fibers. Figure 3 The DS of carboxymethylation of hemp biomass and hardwood fiber are shown in Figure 2. It has been observed that when all samples were treated with the same conditions and chemical environment, the DS of the hemp mixture was the highest, followed by the hemp stalk core, and the lowest was hardwood. By increasing the amount of treatment chemicals (monochloroacetic acid or sodium salt), higher DS hemp stalk core samples were obtained. These DS values ​​are directly related to the generation of MFC by mechanical treatment. Figure 4 It was shown that unmodified hemp stalk core and carboxymethylated hardwood consumed the highest amount of energy in microfibrillation and the production of MFC.

[0224] Energy consumption and fine fiber levels:

[0225] The cumulative energy consumption for producing microfibrillated cellulose from different fibers varies significantly with primary fines level, fiber type, fiber modification and degree of substitution. It has been observed that among the various untreated fibers, CPH has the highest number of primary fines, followed by hemp stalks and softwood has the lowest number of primary fines. Figure 5 From the energy consumption graph in , it can be observed that CPH consumed the lowest energy for the preparation of MFC, while unmodified hardwood fibers consumed the highest level of energy. After fiber modification, fine fibers of hemp stalk core increased, which also helped to reduce the energy consumption in the manufacture of MFC. On the other hand, due to the low DP of periodate oxidized cellulose, periodate oxidized fibers consumed the lowest energy among various modified fibers. Carboxymethylated cellulose of hardwood consumed the highest energy compared to carboxymethylated hemp stalk core and hemp blends. It has also been shown that fibers with higher carboxymethylation DS consume less energy but achieve a higher degree of fibrillation.

[0226] A direct correlation was observed between fiber length and fiber modification and MFC production by mechanical grinding. For all types of fibers, fiber length decreased with fiber modification and mechanical grinding (chemical modification and mechanical treatment). Figure 6 The fines level also increased after fiber modification and mechanical treatment.

[0227] Among various modifications, it was observed that the carboxymethylation of hemp generated a fines level higher than that of periodate oxidation. Without being bound by any one theory, it is believed that this is due to the longer processing time associated with carboxymethylation compared to periodate oxidation. It was also observed that CPH-MFC had a fiber length lower than any other unmodified or modified fiber. The fiber length and fines content numbers before mechanical grinding support energy consumption, because longer and unmodified fibers consume a higher amount of energy for microfibrillation.

[0228] Degree of Polymerization:

[0229] The degree of polymerization (DP) in the cellulose fibers is calculated indirectly by measuring the viscosity of unmodified and modified MFC. Higher viscosity indicates a higher average DP, which in turn indicates stronger bonds in the pulp. Figure 7 The DP of MFC prepared from carboxymethylated cellulose, periodate oxidized cellulose and carboxymethylated-periodate oxidized cellulose is shown. CMPI-modified MFC and PI-modified MFC have lower DP due to the decomposition of AUG units of cellulose chains and the formation of dialdehyde groups. The cleavage of cellulose chains will reduce fiber length and increase fine fiber content. On the other hand, MFC modified by carboxymethylation alone has the highest DP because carboxymethylation does not destroy cellulose chains.

[0230] Surface charge and carboxyl content:

[0231] Surface charge is an important parameter in papermaking, which plays a role through the electronic interaction of charged solubles and the interaction of particles ( et al., 2011). Surface charge also affects the swelling capacity of cellulose fibers and provides a driving force for the adsorption of sizing agents, retention aids, and strength enhancers (Dang et al., 2007). It also affects the post-treatment of fibers, such as enzyme treatment and composite material development (Zhang et al., 2016). Figure 8 The anionic charge of various modified and unmodified MFC samples is shown. It can be clearly seen from the figure that carboxymethylated non-wood fibers (e.g., hemp stalk core and hemp blend) have the highest amount of negative charge, while commercial grade MFC has the lowest amount of negative charge. Since carboxymethylation helps in enhancing the anionic charge of the fiber, it has also been observed that higher DS of carboxymethylation contributes to higher negative charge. The presence of anionic charge is useful in the preparation of biocomposites of MFC as it enhances the bonding of MFC with other polymers. On the other hand, the amount of carboxyl groups shows a similar trend as the surface charge. Carboxymethylation of hemp biomass helps in increasing the amount of carboxyl groups (see Fig. 9 ), while periodate oxidation had little or no effect in increasing the amount of carboxyl groups in the modified fibers. The higher DS hemp stalk core samples resulted in an increase in the amount of carboxyl groups in the fibers compared to the lower DS hemp stalk core fibers. The relatively higher amount of surface charge in the carboxymethylated fibers is due to the higher amount of carboxyl groups, fatty acids, hemicellulose, and phenolic groups of lignin (Sjostrom, 1989).

[0232] The presence of a higher number of anionic charges and carboxyl groups will promote better entanglement by providing hydrogen bonding, which can help increase the burst and tensile strength of the fiber (Belle & Odermatt, 2016). The carboxyl groups can also act as binding sites to achieve controlled chemical loading and release by regulating the interaction between the chemicals and the carboxyl groups (Ghorpade et al., 2017).

[0233] form:

[0234] Fig.10 Scanning electron microscope (SEM) images of MFCs from modified and unmodified hemp stalk cores are shown in FIG. Fig.11Transmission electron microscope (TEM) images are shown in Figure 2. From the SEM images, it is observed that the MFC fiber is highly fibrillated and dispersed, which is a positive embodiment of the quality of MFC. Both modified and unmodified MFC are well dispersed and form a film-like structure, indicating that MFC is suitable for high barrier flexible films and coatings (e.g., paper coatings), such as for use in food packaging to replace disposable plastic-based materials. TEM images show more details of fiber morphology, such as the flat nature of modified and unmodified MFC. Carboxymethylated hemp stalk core MFC is highly fibrillated and forms a film. Periodate-modified hemp stalk core MFC shows that some nanoparticle-like materials are distributed along the flat fibers. All MFCs have formed transparent films, again showing that they are suitable for use in high barrier flexible packaging.

[0235] In summary, renewable and biodegradable microfibrillated cellulose fibers were prepared to obtain low-cost functional composites with improved properties for advanced applications in packaging and other fields. In order to enhance the interaction between the hydrophilic fiber surface and the polymer matrix, the fibers were mildly surface modified under aqueous conditions to add different functional groups to the fibers. Carboxymethylation, periodate oxidation, and carboxymethylation followed by periodate oxidation were performed to add new functional groups on the fiber surface for better adhesion to the polymer matrix. FTIR confirmed the success of fiber modification. The presence of carboxymethyl and dialdehyde groups were observed in CMC and periodate oxidized fibers, respectively. Carboxymethylation of the fibers significantly enhanced the carboxyl content and anionic charge content. Higher DS contributes to a larger amount of anionic charge and carboxyl content, which will enhance adhesion and binding affinity to polymer materials. On the other hand, dialdehyde cellulose generated by periodate oxidation of hemp biomass has a lower degree of polymerization, but microfibrillation consumes significantly less energy. It was also observed that fiber modification helps to increase the fine fiber content and reduce fiber length. The fine fibers of higher amount and the length of reduction can reduce the energy consumption during the mechanical treatment of generating microfibrillated cellulose.The morphological study that carries out via TEM and SEM shows that MFC (for example, from hemp stalk core) can form transparent film-like structure, shows that it is suitable for high barrier packaging.Generating MFC from non-wood biomass at low cost helps to make the waste biomass value, and reduces the use of conventional wood fiber potentially.The biocomposite material developed by these alternative materials can be cost-effective and have improved character, and this can strengthen the barrier properties of paper and packaging material.

[0236] Example 5

[0237] Preparation of composite materials

[0238] Material:

[0239] Microfibrillated cellulose (MFC) was prepared using hemp husks (HH), hemp mixture (HM), autohydrolyzed hemp husks (AH-HH), cocoa pod shells (CPH), and unbleached cocoa pod shells (UCPH). For the modified MFC, pulp fibers were first modified by performing the following chemical modifications: carboxymethylation (CM) (Sim, 2015); periodate oxidation (PI) (Coseri et al., 2013); and carboxymethylation followed by periodate oxidation (CMPI). Other biopolymers used to prepare the composites included: chitosan (medium MW), cationic starch, and glycerol (99%). Chitosan was purchased from Thermo Fisher Scientific (Waltham, MA, USA) in powder form. Cationic starch (Cato 237) was provided by Ingredion (Westchester, IL, USA) in powder form.

[0240] In brief, use the top-down method (Chauhan & Chakrabarti, 2012) to prepare MFC from modified and unmodified hemp stalk core, hemp mixture and cocoa pod shell fiber.Use Lightning mixer to prepare the suspension of MFC from 3-4 weight % of each sample, mix for 15 minutes to obtain a consistent fiber suspension.Then make the suspension of pulp pass through Masuko Super Mass collision machine (Masuko Sangyo Co.Ltd., Japan), which is equipped with silicon carbonate grinding stone (E6-46 DD), and the rotating speed is 2400rpm, with further fibrillation.When pulp passes through, the gap between the upper grinding machine and the lower grinding machine remains negative.Be that the samples are collected after fibrillation under different cumulative energies.Take three aliquots from each sample and dry for 24 hours to obtain solid content, and then average to obtain average solid content value.

[0241] 3% chitosan solution (CH) and cationic starch solution were prepared according to previous protocols (Tokarz, 2006)(Tyagi et al., 2019). Table 2 below shows the pulp samples, fiber types, biopolymers (such as chitosan solution (CH), cationic starch (St) and glycerol) used to prepare the composite films and their processing conditions. Medium molecular weight chitosan and glycerol were purchased from Sigma-Aldrich (St. Louis, MO, USA). Two different temperature conditions were used: 80F and room temperature RT.

[0242] Table 2: Film Coating Formulations (Target Solids - 2.3%, Mixing Time - 30 minutes)

[0243]

[0244]

[0245] All MFC composite solutions were prepared and used in several experiments. Coated films were prepared by solvent casting. Fig.12 The films and casting solutions were analyzed using the methods described below.

[0246] Wet coating properties:

[0247] Apparent viscosity was measured according to TAPPI T 648OM-14 using a Brookfield DV-III Ultra Viscometer (Broodfield Engineering Laboratories, Inc., Middleboro, MA, USA) with a No. 5 spindle at a speed range of 25-250 rpm at 20°C.

[0248] Morphology and chemical properties:

[0249] The surface morphology of the film samples was examined using a FEI Verios 460L field emission scanning electron microscope (SEM) at an accelerating voltage of 2 kV and a current of 13 pA. Prior to imaging, the samples were sputter coated with a thin layer of gold at a coating rate of 7 nm / min in a low vacuum of 90 mTorr Ar gas with an accelerating voltage of 600 V for 3 minutes. The chemical characterization of the film surface was performed using a Bruker-Opus attenuated total reflection-Fourier transform infrared (ATR-FTIR) instrument (Bruker, Billerica, MA, USA) at 400 to 6000 cm -1 The wave number range is 4 cm. -1 , 64 scans. Fiber characterization of each paper type was performed using the TAPPI T271 method with a HiRes Fiber Quality Analyzer (FQA) from OpTest Equipment (Hawkesbury, Ontario, Canada).

[0250] Barrier properties:

[0251] The barrier properties of the films such as water resistance, water vapor transmission rate (WVTR), air permeation resistance and oil and grease resistance (OGR) were measured. WVTR was tested using the water cup method according to ASTM E-96 test method using a standard cup from Thwing-Albert Instrument Company (West Berlin, NJ, USA). For air permeation resistance, TAPPI's Air Resistance 'Gurley Densitometer Method' T460 was used. The results are reported as Gurley seconds per 100 ml of air displaced (Gs / 100 ml). OGR and OGR crease test were tested by performing a 3M Scotchban test, which has been adopted under TAPPI T559. The results are reported as a kit number from 1 to 12. The OGR crease test was performed by creased the film using a 10 kg roller. Hot oil testing (65°C, 20 minutes) using Mazola oil and ambient oil testing (overnight at room temperature) using sunflower oil were performed as described below to analyze the oil absorption of the film. Water resistance of the samples was also tested at different time intervals.

[0252] More specifically, regarding hot oil testing, a FOODSERVICE PACKAGING The test procedure of the FPI standard "Harmonized Hot Oil Test For Printed, Finished Foodservice Products" (2013 update) has been modified to provide testing for films and coated papers. Typically, the test uses dyed oil to determine the grease resistance and penetration of films or coated papers used for packaging and other related products.

[0253] The hot oil test is performed using the following materials: Mazola corn oil or another type of oil; red dye (e.g., D53004, sold under the trade name Red IK Liquid sold by Chromatech Inc., Canton, Michigan, USA); glass or steel beaker; hot plate capable of maintaining an oil temperature of 65°C-68°C (150°F-155°F); laboratory thermometer; bracket used to position the specimen to maintain ink contact with the top surface of the specimen during testing, test area 16 cm 2 (as seen in the Tappi T530 sizing test (Hercules-type method) with ink resistance test paper); and a container for the waste oil, a paper towel, and a stopwatch. To conduct the test, a 45 cm 2 Prepare the specimen by cutting the coated paper or film specimen into a circular shape to allow for proper clamping and avoid any leakage. The test procedure is described below. See also Fig.18 .

[0254] Testing Procedure:

[0255] Quantitatively pipette 3.8 ml of red dye into one gallon of corn oil and mix thoroughly to a concentration of 0.1%. Prepare a new solution at least every six months.

[0256] Measure the initial weight of the sample.

[0257] Place the sample holder on a flat surface.

[0258] Place a paper towel over the base of the sample holder.

[0259] The specimen is placed on top of the paper towel and the flexible ring is clamped to secure the specimen and paper towel in place.

[0260] Heat the dyed corn oil to 65°C-68°C (150°F-155°F) in a 300 ml beaker. Maintain the temperature by controlling the temperature with a hot plate.

[0261] Take 10 ml of the heated oil and pour it into the sample holder.

[0262] Allow the sample to sit for 20 minutes.

[0263] After 20 minutes, pour the oil from the sample holder into a holding container.

[0264] Wipe off the remaining oil with a paper towel and immediately check the back of the specimen for saturation and mark these areas with a pen or pencil. Check the back of the specimen for stains. If there is stain on the bottom of the specimen but no penetration, it is not considered a failure. If this occurs, the sample passes the test.

[0265] Inspect the specimen for signs of soaking through the paper towel. Any oil found on the paper towel will result in a failure. If no oil is found on the paper towel, the specimen will pass the test.

[0266] After wiping off the oil on the specimen, take the final weight of the specimen.

[0267] Repeat the above procedure for the remaining specimens using the same order as for filling the specimens, inspecting each specimen after 20 minutes.

[0268] calculate:

[0269] Weight gain in g = (final weight of sample - initial weight of sample) g

[0270] Hot oil absorption, g / m 2 = (final weight of the sample – initial weight of the sample) g / flexible ring area (0.0016m 2 )

[0271] The room temperature oil absorption test was performed using the same procedure except that 10 ml of room temperature (22°C-23°C) sunflower oil was poured into the sample holder and the sample was left overnight.

[0272] Mechanical testing:

[0273] The tensile strength of the films was analyzed according to TAPPI T 494 method.

[0274] Fourier Transform Infrared Spectroscopy (FTIR):

[0275] Use the product name SPECTRUM TM FTIR spectra of polymers (starch and chitosan), microfibrillated cellulose (MFC), and composites were recorded using a PerkinElmer spectrometer sold by PerkinElmer Corporation (Waltham, MA, USA). Each sample was placed in the contact area of ​​an attenuated total reflectance (ATR) diamond crystal with a circle of ~1.5 mm diameter. All spectra were obtained between 4000 and 500 cm -1 Each sample was scanned 20 times with a resolution of 4 cm -1 A baseline correction was performed before analyzing the samples and all spectra were collected at the same baseline.

[0276] discuss:

[0277] All different films were developed in four different trials and their properties were analyzed. Table 3 below provides a summary of the basis weight, bulk volume, strength properties, and barrier properties of the films.

[0278] Tables 4 and 5 provide data from the hot oil absorption and room temperature oil absorption tests, respectively.

[0279]

[0280]

[0281]

[0282]

[0283]

[0284] Figures 13A-13EThe variation of viscosity with rpm is shown. The composite solutions with chitosan and glycerol showed the highest viscosity at room temperature in both the case of modified and unmodified MFC. A similar trend was observed in the case of CPH-based membrane solutions. Based on this trend, it can be inferred that bond formation or network formation between the anionic carboxyl groups and the cationic amine groups from chitosan has occurred (Heggset et al., 2017). However, the effect of temperature is not fully understood since the heating treatment causes changes in the moisture content. For all these coating solutions, the viscosity decreased with increasing rpm or shear rate during shear, thereby showing a shear-thinning behavior of the coating solutions, which is ideal during coating applications (Tyagi et al., 2018).

[0285] Accumulation volume:

[0286] Bulk volume is an important property of packaged products. It can affect porosity, pore volume, thickness, liquid absorption and air / gas permeability (Kartovaara et al., 1985). CPH films made from direct pulp or MFC have significantly high bulk volumes. See Figures 14A-14D Without being bound by any one theory, it is believed that this is related to the nature of the fiber and the composition of cocoa husk, which has a high pectin content compared to other pulps (Daud et al., 2013).

[0287] Fiber morphology:

[0288] Figures 15A-15C SEM images of MFC films under different conditions are shown. From the images, it can be inferred that most of the MFC films show good uniformity, which contributes to good barrier properties. Especially in the case of films prepared under higher temperature conditions, the films show good uniformity. For example, compare the images of carboxymethylated composite films with chitosan and glycerol prepared at room temperature and at 80 °C. See Fig. 15B and 15C At 1000x magnification, the films prepared at elevated temperature appear more uniform than the films prepared at room temperature. Without being bound by any one reason, it is believed that this can be attributed to the higher temperature leading to better interactions between MFC, chitosan, and glycerol.

[0289] FTIR Spectroscopy:

[0290] Figures 16A-16D FTIR spectra of various polymers, MFCs and composites are shown. -1 The peaks appearing in the region are attributed to the stretching vibrations of the primary and secondary hydroxyl groups of carbohydrates. This stretching vibration is not present in starch and chitosan polymers.-1 The peaks at represent aromatic esters, ethers, and phenolic compounds, respectively, which are absent in the spectra of starch and chitosan (Tanpichai et al., 2019).

[0291] 1648-1678cm in CM, PI and CMPI modified cellulose, unmodified cellulose and their composites -1 The peak at 2900 cm-1 is related to the presence of C=O stretching from carboxyl and keto groups of modified MFC or polymers (Pelissari et al., 2014). -1 The peaks at 3400 cm are attributed to symmetric and asymmetric CH stretching, while the peaks at 3400 cm -1 The peak at is characteristic of the OH stretching of cellulose (Cui et al., 2016). The stretching vibration of C=O in the composite was slightly shifted to the right due to the presence of glycerol in the composite. The absence of any unique peak in the chitosan-based composites led to the speculation that the cross-linking between MFC and chitosan is based on the physical interaction between the reducing ends of cellulose and the primary amines of chitosan, which promotes the dehydration of chitosan (Stefanescu et al., 2012)(Benghanem et al., 2017). See Fig.17 A similar explanation can be given for starch-based composites.

[0292] Oil Absorption:

[0293] Oil resistance can be a consideration for films and coated papers used in packaging applications. The currently disclosed films have been tested for barrier properties by a 20 minute hot oil test and a 15 hour room temperature oil test. See Fig.18 and 19A -19D. See also Tables 4 and 5 above. The presently disclosed membranes showed good results in both hot oil resistance and room temperature oil resistance. All tested membranes passed the hot oil test (see Fig.18 ), there are no stains on the paper towel. Fig.19A and 19B The weight gain of films prepared from different modified and unmodified MFC composites of the presently disclosed subject matter in a hot oil test is shown. The highest weight gain of the films tested was 1.98% (1.19 gsm), which is well below the 5% weight gain acceptable value (Foodservice packaging institute, FPI). Overall, relatively high weight gain percentages were observed for the unmodified hemp MFC composites, while the modified hemp MFC composites showed less weight gain, especially those with cationic starch. See Fig.19A, e.g., circled bars. It was also observed that films made from formulations formed at 80°C gained less weight than films made from formulations formed at room temperature. Without being bound by any one theory, it is believed that this is related to improved mixing at higher temperatures and enhanced interactions between the functional groups of the MFC and other polymers in the composite.

[0294] The weight gain of the film in the oil absorption test also depends on the basis weight of the film. Films with higher basis weights gain less weight, while films with lower basis weights (e.g., basis weights less than 10 gsm) gain more weight. Similar weight gain trends were observed when the ambient oil test was conducted for a longer period of time. See Fig.19C and 19D .

[0295] Measuring the WVTR rate of hemp-based MFC membranes. Figures 20A-20D The films containing carboxymethylated and unmodified hemp stalk core showed consistency in WVTR values ​​(10-20 g / m 2 .mm / day). However, the films based on cocoa pod shell (CPH) slurry showed high WVTR values ​​compared to the films based on CPH MFC. Fig. 20A This may be due to the morphology and distribution of the fibers as well as the composition, since CPH has a high pectin content and shorter fibers have better orientation than longer fibers (Daud et al., 2013). The hemp blend based MFC composite membranes also showed relatively high WVTR values ​​compared to the hemp stalk core based MFC membranes. Fig. 20B MFC composite membranes based on hemp blends also generally have lower densities than MFC composite membranes based on hemp stalk core. Fig.20E The WVTR data were compared with the membrane density. Fig.20F Films with higher density generally have lower WVTR.

[0296] Oil and Grease Resistance:

[0297] For oil and grease resistance, 12 kit solutions made of different ratios of hexane, toluene, and castor oil were used. As the kit number increased, the amount of hexane and toluene solvents in the kit solution increased, while the amount of castor oil decreased. Thus, at higher kit numbers, penetration of the kit solution through the paper became more favorable due to the lower viscosity of the kit solution and due to the relatively non-polar nature of the kit solution. All of the films tested, except the cocoa pod shell membrane, passed the Kit No. 12 test. For exemplary images of films that passed or failed the kit test, see Fig.21A and 21BThe 100% CPH membrane failed the test under Kit No. 3, the CPH membrane with 20% chitosan prepared at 80°C failed the test under Kit No. 7, and the CPH membrane with 80% chitosan and 2% glycerol prepared at 80°C failed the test under Kit No. 5. Without being bound by any one theory, it is believed that these results are based on the fact that the CPH membranes are made of more porous pulp than the corresponding MFC membranes, and that the fiber bonding in the MFC-based membranes is higher than in conventional membranes due to the influence of fine fibers (Kullander et al., 2012).

[0298] A sample that has passed the Kit No. 12 test was creased with a 10 kg roller and then the Kit solution was applied. Fig. 22 Both the creased and uncreased samples passed the Kit No. 12 test.

[0299] Water resistance:

[0300] To measure water resistance, a sample was taken from the membrane and the weight of the sample was measured. Then, the sample was placed in water and the weight of the sample was remeasured at different time intervals. While the unmodified 100% CPH MFC membrane began to fall apart after two hours, almost all other membranes tested remained intact even after 32 days. See Figures 23A-23C .

[0301] Gas Barrier:

[0302] Air resistance was measured for the different film samples. Except for the CPH film made from direct pulp, all the films tested showed Gurley seconds above 3000 (higher Gurley seconds or units correspond to lower permeability). Without being bound by any one theory, it is believed that this result is related to the high percentage of fines and high fiber-fiber bonding in the MFC samples. The samples with chitosan and glycerol prepared at room temperature showed the highest air resistance (see Fig.24 ), which indicates proper entanglement between biopolymer and pulp at room temperature.

[0303] Tensile properties:

[0304] The tensile index of the film was measured to assess its strength properties, since strength may be a property of interest for packaged products. Several tests were performed to analyze the data. Figures 25A-25D .like Fig.25A , 25C As shown in Figures 25 and 25D, in three different experiments, the membranes prepared from the composites based on carboxymethylated hemp core MFC showed relatively better strength than the membranes containing unmodified hemp core MFC. The reason may be due to the better physical networking / cross-linking between the biopolymers in the case of the modified MFC. This was also observed in the SEM images. See Figures 15A-15C Without being bound by any one theory, it is believed that higher crosslinking is associated with a higher number of carboxyl groups on the carboxymethylated MFC (see Fig. 9 ), a higher number of carboxyl groups can help form a better network. In addition, during the preparation of MFC, it was observed that the modified MFC had a higher fine fiber content than the unmodified MFC (see Figure 6 ), which could contribute to better strength. However, a different trend was observed in the case of MFC composites based on hemp blends. Fig.25B Without being bound by any one theory, it is believed that this result is due to the nature of the fibers themselves, as the hemp blend is a combination of long fibers and a small amount of short fibers. It was also observed that the tensile index was generally relatively high for films produced from formulations mixed at higher temperatures, especially where the composites also contained starch, presumably due to better crosslinking between the biopolymers. In the case of blends of modified MFCs, especially for PI-MFC (see Fig.25D ), the membrane preparations were prepared at room temperature because at high temperatures, PI-MFC tends to form brittle films. However, these membranes still exhibited good strength. Although the values ​​varied from experiment to experiment, the lowest values ​​were observed for the membranes containing CM-PI-MFC and chitosan prepared at high temperature. This is presumably a result of fiber agglomeration. A similar trend was observed when measuring the elongation values. See Figures 26A-26D .

[0305] In summary, the film / coating development of MFC based on agricultural residues and byproducts was evaluated to develop flexible packaging. MFC was prepared from a mixture of high κ kraft pulped hemp stalk core and autohydrolysis (almost chemical-free) pulped hemp stalk core, high κ kraft conventional bleached and unbleached cocoa pod shells, and high κ kraft enzyme-treated conventional bleached hemp. Different types of chemical modifications were performed on the pulp to prepare modified MFC. Different types of MFC were used with biopolymers (such as chitosan, glycerol, AKD and cationic starch) in different ratios and at two different temperatures to prepare composite films. All films were flexible and showed high barrier properties. For example, the films showed high oil resistance, grease resistance, water resistance and air resistance. The films based on the modified MFC also had good strength properties. In repeated tests, the data showed consistency, and the barrier properties of low basis weight films were measured. Based on these data, the currently disclosed film composites show good quality for coating purposes.

[0306] References

[0307] All references listed below, as well as all references cited in this disclosure, including but not limited to all patents, patent applications and publications, scientific journal articles and database entries thereof, are incorporated herein by reference in their entirety to the extent that they supplement, explain, provide context for, or teach the methods, techniques and / or compositions employed herein.

[0308] Agate,S.;Tyagi,P.;Naithani,V.;Lucia,L.;Pal,L.(2020).InnovatingGeneration of Nanocellulose from Industrial Hemp by Dual AsymmetricCentrifugation.ACS Sustain.Chem.Eng.,8(4),1850–1858.

[0309] Belle,J.,&Odermatt,J.(2016).Initial wet web strength ofpaper.Cellulose,23(4),2249–2272.

[0310] Benghanem, S.; Chetouani, A.; Elkolli, M.; Bounekhel, M.; Benachour, D. (2017). Effects of Physical and Chemical Modification on Biological Activities of Chitosan / Carboxymethylcelluse Based Hydrogels. J. Chil. Chem. Soc., 62(1), 3376–3380.

[0311] Brodeur,G.,Yau,E.,Badal,K.,Collier,J.,Ramachandran,KB,Ramakrishnan,S.(2019).www.hindawi.com / journals / er / 2011 / 787532 / abs / (accessed:July 2019).

[0312] Bruce,C.,Nilsson,C., E.,& L.(2015).Paper-sheetbiocomposites based on wood pulp grafted with poly(ε-caprolactone).Journal ofApplied Polymer Science,132(23);doi.org / 10.1002 / app.42039.

[0313] Chang,C.,Duan,B.,Cai,J.,Zhang,L.(2010).Superabsorbant hydrogels basedon cellulose for smart swelling and controllabledelivery.Eur.Polym.J.,46,92-100.

[0314] Chauhan,V.,&Chakrabarti,S.(2012).Use of nanotechnology for highperformance cellulosic and papermaking products.Cellulose Chemistry andTechnology,46,389.

[0315] Chinga-Carrasco,G.,&Syverud,K.(2014).Pretreatment-dependent surfacechemistry of wood nanocellulose for pH-sensitive hydrogels.Journal ofBiomaterials Applications,29(3),423–432.

[0316] CM-15:88,S.-C.(1998).Viscosity in Cupri-Ethylenediamine(CED)Solution.SCAN.

[0317] Coseri,S.,Biliuta,G.,Simionescu,B.C.,Stana-Kleinschek,K.,Ribitsch,V.,&Harabagiu,V.(2013).Oxidized cellulose—Survey of the most recentachievements.Carbohydrate Polymers,93(1),207–215.

[0318] Cui,S.;Zhang,S.;Ge,S.;Xiong,L.;Sun,Q.(2016).Green Preparation andCharacterization of Size-Controlled Nanocrystalline Cellulose via Ultrasonic-Assisted Enzymatic Hydrolysis.Ind.Crops Prod.,83,346–352.

[0319] Dang,Z.,Elder,T.,&Ragauskas,A.J.(2007).Alkaline peroxide treatment ofECF bleached softwood kraft pulps.Part 1.Characterizing the effect ofalkaline peroxide treatment on carboxyl groups of fibers.Holzforschung,61(4),445–450.

[0320] Darmadji,P.;Izumimoto,M.(1994).Effect of Chitosan in MeatPreservation.Meat Sci.,38(2),243–254.

[0321] Daud,Z.;Sari,A.;Kassim,M.;Aripin,A.M.;Awang,H.;Hatta,Z.M.;Education,V.;Tun,U.;Onn,H.;Pahat,B.(2013).Chemical Composition and Morphological ofCocoa Pod Husks and Cassava Peels for Pulp and Paper Production.Aust.J.BasicAppl.Sci.,7(9),406–411.

[0322] Edyta,M.,Piotr,P.,Marcin,D.,&Kamila,B.(2015).Comparison ofpapermaking potential of wood and hemp cellulose pulps.Annals of WarsawUniversity of Life Sciences-SGGW.Forestry and Wood Technology,91,134–137.

[0323] Elazzouzi-Hafraoui,S.,Nishiyama,Y.,Putaux,J.-L.,Heux,L.,Dubreuil,F.,&Rochas,C.(2008).The Shape and Size Distribution of Crystalline NanoparticlesPrepared by Acid Hydrolysis of Native Cellulose.Biomacromolecules,9(1),57–65.

[0324] Evans,R.,&Wallis,A.F.A.(1989).Cellulose molecular weights determinedby viscometry.Journal of Applied Polymer Science,37(8),2331–2340.

[0325] Fengel,D.(1992).Wood and cellulose chemistry.Holz Als Roh-UndWerkstoff,50(9),340.

[0326] Ghorpade,V.S.,Yadav,A.V.,&Dias,R.J.(2017).Citric acid crosslinkedβ-cyclodextrin / carboxymethylcellulose hydrogel films for controlled delivery ofpoorly soluble drugs.Carbohydrate Polymers,164,339–348.

[0327] J.L.,Frollini,E.,da Silva,C.G.,Wypych,F.,&Satyanarayana,K.G.(2009).Characterization of banana,sugarcane bagasse and sponge gourdfibers of Brazil.Industrial Crops and Products,30(3),407–415.

[0328] Gulsoy,S.K.(2014).Effects of Cationic Starch Addition and PulpBeating on Strength Properties of Softwood Kraft Pulp.Starch / Staerke.,66(7–8),655–659.

[0329] Gustafson,R.R.;Sleicher,C.A.;McKean,W.T.;Finlayso,B.A.(1983).Ind.Eng.Chem.Process Des.Dev.,22,87.

[0330] Gutta,R.,Wan,H.Da,&Kuriger,G.(2013).Packaging materials selectiontool considering environmental sustainability.IIE Annual Conference and Expo2013,3706–3715.

[0331] Hamzeh,Y.;Sabbaghi,S.;Ashori,A.;Abdulkhani,A.;Soltani,F.(2013).Improving Wet and Dry Strength Properties of Recycled Old Corrugated Carton(OCC)Pulp Using Various Polymers.Carbohydr.Polym.,94(1),577–583.

[0332] Heggset,E.B.;Chinga-Carrasco,G.;Syverud,K.(2017).TemperatureStability ofNanocellulose Dispersions.Carbohydr.Polym.,157,114–121.

[0333] Heinze,T,&Liebert,T.(2001).Unconventional methods in cellulosefunctionalization.Progress in Polymer Science,26(9),1689–1762.

[0334] Heinze,Thomas,&Koschella,A.(2005).Carboxymethyl Ethers of Celluloseand Starch–A Review.Macromolecular Symposia,223(1),13–40.

[0335] Heinze,Thomas,&Pfeiffer,K.(1999).Studies on the synthesis andcharacterization of carboxymethylcellulose.Die Angewandte MakromolekulareChemie,266(1),37–45.

[0336] Jambeck,J.R.;Geyer,R;Wilcox,C.;Siegler,T.R.;Perryman,M.;Andrady,A.;Narayan,R.;Law,K.L.(2015).Science,347(6223),768-771.

[0337] Jo,C.;Lee,J.W.;Lee,K.H.;Byun,M.W.(2001)Quality Properties of PorkSausage Prepared with Water-Soluble Chitosan Oligomer.Meat Sci.59(4),369–375.

[0338] Kartovaara,I.;Rajala,R.;Lüukkala,M.V;Sipi,K.Conduction of Heat inPaper;V.Punton,M.E.P.,Ed.;London,UK,1985.

[0339] Khan,A.;Khan,R.A.;Salmieri,S.;Le Tien,C.;Riedl,B.;Bouchard,J.;Chauve,G.;Tan,V.;Kamal,M.R.;Lacroix,M.(2012).Mechanical and Barrier PropertiesofNanocrystalline Cellulose Reinforced Chitosan Based NanocompositeFilms.Carbohydr.Polym.,90(4),1601–1608.

[0340] Khullar,R.,Varshney,V.K.,Naithani,S.,Heinze,T.,&Soni,P.L.(2005).Carboxymethylation of cellulosic material(average degree of polymerization2600)isolated from cotton(Gossypium)linters with respect to degree ofsubstitution and rheological behavior.Journal of Applied Polymer Science,96(4),1477–1482.

[0341] Kim,U.-J.,&Kuga,S.(2001).Ion-exchange chromatography by dicarboxylcellulose gel.Journal of Chromatography.A,919,29–37.

[0342] Kim,K.W.;Min,B.J.;Kim,Y.T.;Kimmel,R.M.;Cooksey,K.;Park,S.I.(2011).Antimicrobial Activity against Foodborne Pathogens of Chitosan BiopolymerFilms of Different Molecular Weights.LWT-Food Sci.Technol.,44(2),565–569.

[0343] Kullander,J.;Nilsson,L.;Barbier,C.Evaluation of Furnishes for TissueManufacturing;Wet Pressing;2012;Vol.27,947-951.

[0344] Landoll,L.M.(1982).Nonionic polymer surfactants.Journal of PolymerScience:Polymer Chemistry Edition,20(2),443–455.

[0345] Lavoine,N.;Desloges,I.;Dufresne,A.;Bras,J.(2012).MicrofibrillatedCellulose-Its Barrier Properties and Applications in Cellulosic Materials:AReview.Carbohydr.Polym.,90(2),735–764.

[0346] K.,Saukkonen,E.,Kajanto,I.,& J.(2011).The effectofhemicellulose extraction on fiber charge properties and retention behaviorof kraft pulp fibers.Bioresources,6,219.

[0347] MacArthur D.,Waugray D.,Stutchey M.(2016).The New Plastics Economy,rethinking the Future of Plastics.World Economic Forum.

[0348] Mali,K.,Dhawale,S.,Dias,R.,Dhane,N.,&Ghorpade,V.(2018).Citric AcidCrosslinked Carboxymethyl Cellulose-based Composite Hydrogel Films for DrugDelivery.Indian Journal of Pharmaceutical Sciences,80,657–667.

[0349] Moussa,I.,Khiari,R.,Moussa,A.,Belgacem,M.N.,&Mhenni,M.F.(2019).Preparation and Characterization of Carboxymethyl Cellulose with a HighDegree of Substitution from Agricultural Wastes.Fibers and Polymers,20(5),933–943.

[0350] Moutou,K.A.Panagiotaki,P.Mamuris,Z.(2004).Pulps.Determination oflimiting viscosity number in cupri-ethylenediamine(CED)solution.

[0351] Nevell,T.P.(1957).35—THE MECHANISM OF THE OXIDATION OF CELLULOSE BYPERIODATE.Journal of the Textile Institute Transactions,48(12),T484–T494.

[0352] No,H.K.;Meyers,S.P.;Prinyawiwatkul,W.;Xu,Z.(2007).Applications ofChitosan for Improvement of Quality and ShelfLife of Foods:A Review.J.FoodSci.,72(5).

[0353] Odio,M.,&Friedlander,S.(2000).Diaper dermatitis and advances indiaper technology.Current Opinion in Pediatrics,12,342–346.

[0354] Pelissari,F.M.,Sobral,P.J.do A.,&Menegalli,F.C.(2014).Isolation andcharacterization of cellulose nanofibers from banana peels.Cellulose,21(1),417–432.

[0355] Pushpamalar,V.,Langford,S.J.,Ahmad,M.,&Lim,Y.Y.(2006).Optimization ofreaction conditions for preparing carboxymethyl cellulose from sagowaste.Carbohydrate Polymers,64(2),312–318.

[0356] Ranby,B.R.,Banderet,A.,&Sillén,L.G.(1949).Aqueous Colloidal Solutionsof Cellulose Micelles.Acta Chemica Scandinavica,3,649–650.

[0357] Sareena,C.,Sreejith,M.P.,Ramesan,M.T.,&Purushothaman,E.(2013).Biodegradation behaviour of natural rubber composites reinforced withnatural resource fillers–monitoring by soil burial test.Journal of ReinforcedPlastics and Composites,33(5),412–429.

[0358] Santos RB,Jameel H,Chang HM,Hart PW(2013).Impact of lignin andcarbohydrate chemical structures on kraft pulping processes and biofuelproduction.Tappi Journal,12(7):23–31.

[0359] Sim,G.(2015).Carboxylated Cellulose Pulp Fibers:from Fundamentals toApplications;Ph.D.Thesis;McGill University,Montreal,Canada.

[0360] Sjostrom,E.(1989).The origin of charge on cellulosic fibers.NordicPulp&Paper Research Journal,4(2),90–93.

[0361] Smithers(2018).Market Value Estimations for Packaging in 2018andBeyond.

[0362] Stefanescu,C.;Daly,W.H.;Negulescu,I.I.(2012).Biocomposite FilmsPrepared from Ionic Liquid Solutions of Chitosan andCellulose.Carbohydr.Polym.,87(1),435–443.

[0363] Tanpichai,S.,Biswas,S.K.,Witayakran,S.,&Yano,H.(2019).Water Hyacinth:A Sustainable Lignin-Poor Cellulose Source for the Production of CelluloseNanofibers.ACS Sustainable Chemistry&Engineering,7(23),18884–18893.

[0364] Tarique,J.;Sapuan,S.M.;Khalina,A.(2021).Effect of GlycerolPlasticizer Loading on the Physical,Mechanical,Thermal,and Barrier Propertiesof Arrowroot(Maranta Arundinacea)Starch Biopolymers.Sci.Rep.,11(1),1–17.

[0365] Thygesen,A.,Daniel,G.,Lilholt,H.,&Thomsen,A.B.(2006).Hemp fibermicrostructure and use of fungal defibration to obtain fibers for compositematerials.Journal of Natural Fibers,2(4),19–37.

[0366] Tokarz,M.(2006).Preparation of Cationic Starch Solution.,No.960,1–2.

[0367] Tyagi,P.;Hubbe,M.A.;Lucia,L.;Pal,L.(2018).High PerformanceNanocellulose-Based Composite Coatings for Oil and GreaseResistance.Cellulose,25(6),3377–3391.

[0368] Tyagi,P.,Mathew,R.,Opperman,C.,Jameel,H.,Gonzalez,R.,Lucia,L.,Hubbe,M.,&Pal,L.(2019).High-Strength Antibacterial Chitosan-Cellulose NanocrystalComposite Tissue Paper.Langmuir,35(1),104–112.

[0369] Tyagi,P.,Agate,S . ,Velev,O.D.Lucia,L.Pal,L.(2022)A Critical Review ofthe Performance and Soil Biodegradability Profiles of Biobased Natural andChemically Synthesized Polymers in Industrial Applications,EnvironmentalScience&Technology,56(4),2071-2095,DOI:10.1021 / acs.est.1c04710.

[0370] Vaezi,K.;Asadpour,G.;Sharifi,S.H.(2019).Effect of Coating with NovelBio Nanocomposites of Cationic Starch / Cellulose Nanocrystals on theFundamental Properties of the Packaging Paper.Polym.Test.,80(August).

[0371] Wu,M.,&Kuga,S.(2006).Cationization of cellulose fabrics bypolyallylamine binding.Journal of Applied Polymer Science-J APPL POLYM SCI,100,1668–1672.

[0372] Wu,N.,Wan,X.-F.,&Chai,X.-S.(2018).Rapid determination of degree ofsubstitution of sodium carboxymethylcellulose by headspace gaschromatography.Polymer Testing,71,6–9.

[0373] Yamashita,Y.,Shono,M.,Sasaki,C.,Nakamur,Y.,(2010).Carbohydr.Polym.,79,914.

[0374] Zhang,X.,Tu,M.,Paic,MG(2011).BioEnergy Res.,4,246.

[0375] Zhang,H.,Zhao,C.,Li,Z.,&Li,J.(2016).The fiber charge measurementdepending on the poly-DADMAC accessibility to cellulose fibers.Cellulose,23(1),163–173.

[0376] Zhao,H.,Cheng,F.,Li,G.,&Zhang,J.(2003).Optimization of a process forcarboxymethyl cellulose(CMC)preparation in mixed solvents.International Journal of Polymeric Materials,52,749–759.

[0377] It should be understood that various details of the presently disclosed subject matter can be changed without departing from the scope of the presently disclosed subject matter.In addition, the foregoing description is for the purpose of illustration only, and not for the purpose of limitation.

Claims

1. A packaging material comprising a film or coating comprising agro-based microfibrillated cellulose (A-MFC), wherein the A-MFC comprises microfibrillated cellulose (MFC) prepared from pulp from a non-wood lignocellulosic raw material, wherein the film or coating has a viscosity less than about 5 percent (%) and / or less than about 2.5 grams per square meter (g / m2) when contacted with hot oil for 20 minutes. 2 ) of the invention, wherein the hot oil has a temperature of about 65 degrees Celsius (°C).

2. The packaging material of claim 1, wherein the non-wood lignocellulosic feedstock comprises one or more agricultural residues and / or industrial by-products.

3. The packaging material according to claim 2, wherein the non-wood lignocellulosic raw material is selected from the group consisting of hemp stalk core, a mixture of hemp stalk core and hemp bast, bagasse, cocoa pod shell and combinations thereof.

4. The packaging material according to any one of claims 1 to 3, wherein the A-MFC comprises modified A-MFC, wherein the modified A-MFC comprises MFC derived from chemically modified pulp.

5. The packaging material according to claim 4, wherein the modified A-MFC comprises carboxymethylated A-MFC; oxidized A-MFC; carboxymethylated and oxidized MFC; or a combination thereof.

6. The packaging material according to claim 5, wherein the oxidized A-MFC comprises dialdehyde cellulose.

7. The packaging material of any one of claims 1-6, wherein the film or coating comprises from about 5 weight percent (wt%) to about 90 wt% A-MFC, optionally wherein the film or coating comprises from about 40 wt% A-MFC to about 80 wt% A-MFC.

8. The packaging material according to any one of claims 1 to 7, wherein the film or coating further comprises one or more of chitosan, cationic starch, glycerol, triethyl citrate, polyhydroxyalkanoate (PHA) and alkyl ketene dimer (AKD).

9. The packaging material of any one of claims 1-8, wherein the A-MFC has a total fines level of about 50% to about 95%.

10. The packaging material of any one of claims 1-9, wherein the A-MFC has an average fiber length of about 0.1 mm to about 0.45 mm.

11. The packaging material of any one of claims 1-10, wherein the film or coating has a thickness of about 1 micron to about 200 microns, optionally wherein the film or coating is a coating having a thickness of about 1 micron to about 30 microns or a film having a thickness of about 10 microns to about 200 microns, and optionally wherein the film has a thickness of about 20 microns to about 140 microns.

12. The packaging material according to any one of claims 1 to 11, wherein the film or coating has a viscosity of about 0.5 cubic centimeters per gram (cm 3 / g) to about 2.0cm 3 / g of bulk volume.

13. The packaging material of any one of claims 1 to 12, wherein the film or coating has a viscosity less than about 2% and / or less than about 1.19 g / m 2 of weight gain, wherein the hot oil has a temperature of about 65°C.

14. The packaging material of any one of claims 1-13, wherein the film or coating has a viscosity less than about 3% and / or less than about 1.8 g / m 2 of weight increase.

15. The packaging material according to any one of claims 1 to 14, wherein the film or coating has a viscosity of less than 50 g / m2 mm / day (g / m 2 .mm / day), optionally less than 15g / m 2 .mm / day Water Vapor Transmission Rate (WVTR).

16. The packaging material of any one of claims 1 to 15, wherein the film or coating has a g / cm 3 ) to about 2.1 g / cm 3 density.

17. The packaging material of any one of claims 1-16, wherein the film or coating has a tensile index of about 30 Newton meters per gram (Nm / g) or greater.

18. The packaging material of any one of claims 1-17, wherein the film or coating has a stretchability of about 1.5% or more.

19. The packaging material according to any one of claims 1 to 18, wherein the packaging material is a food or beverage packaging material.

20. The packaging material according to any one of claims 1 to 19, wherein the packaging material further comprises a substrate, wherein the substrate is coated with a film or coating comprising A-MFC on at least one surface, optionally wherein the substrate is a flexible substrate.

21. The packaging material according to claim 20, wherein the substrate comprises paper or another biodegradable and / or sustainable material, optionally wherein the paper comprises or consists of papermaking fibers derived from waste biomass.

22. A method for preparing a film having a viscosity less than about 5 percent (%) and / or less than about 2.5 g / m2 (g / m 2 ), wherein the hot oil has a temperature of about 65 degrees Celsius (° C.), the method comprising: (a) preparing a suspension comprising agro-based microfibrillated cellulose (A-MFC), wherein the A-MFC is microfibrillated cellulose (MFC) prepared from pulp from a non-wood lignocellulosic raw material; (b) forming a web using the suspension; as well as (c) drying the web to provide the film.

23. The method of claim 22, wherein the non-wood lignocellulosic feedstock comprises one or more agricultural residues and / or industrial by-products, optionally wherein the non-wood lignocellulosic feedstock comprises hemp stalk cores, a mixture of hemp stalk cores and hemp bast, cocoa pod shells, or a combination thereof.

24. A method according to claim 22 or claim 23, wherein preparing the suspension comprising A-MFC comprises fibrillating a suspension of pulp from a non-wood lignocellulosic feedstock, wherein the pulp has a primary fines level of more than 10%, optionally wherein the pulp has a primary fines level of about 15% to about 50%.

25. The method of claim 24, wherein the pulp is kraft pulp, autohydrolyzed pulp, unbleached pulp, higher yield pulp, or higher lignin-containing pulp.

26. A method according to claim 24 or claim 25 comprising chemically modifying the pulp in an aqueous medium prior to fibrillation.

27. The method of claim 26, wherein chemically modifying the pulp comprises carboxymethylating the pulp, oxidizing the pulp, or carboxymethylating and oxidizing the pulp.

28. A method according to claim 24 or claim 25 comprising carboxymethylating the pulp either before or after fibrillation.

29. The method of any one of claims 22-28, wherein preparing the suspension comprising A-MFC comprises contacting the A-MFC with a liquid, optionally water, to provide a suspension comprising a total solids content comprising at least about 50 weight percent (wt%) of the A-MFC, optionally providing a suspension comprising a total solids content comprising about 50 wt% to about 80 wt% A-MFC.

30. The method of any one of claims 22-29, wherein the suspension has a solids content of about 2.0% or more and / or about 5% or less.

31. The method according to any one of claims 22-30, wherein the suspension comprising A-MFC further comprises one or more of chitosan, cationic starch, glycerol, triethyl citrate, polyhydroxyalkanoate (PHA) and alkyl ketene dimer (AKD).

32. The method of any one of claims 22-31, wherein preparing the suspension comprises mixing the suspension at a temperature between about room temperature and about 80 degrees Celsius (°C) for a period of time, optionally about 30 minutes.

33. The method of any one of claims 22-32, wherein step (b) comprises casting a web from the suspension.

34. The method of any one of claims 22-33, wherein the method further comprises applying the film to a surface of a substrate, optionally a paper substrate, to provide a film-coated substrate.

35. The method of any one of claims 22-34, wherein the method further comprises forming a packaging material from the film or from a substrate coated with the film.

Citation Information

Patent Citations

  • Barrier film comprising microfibrillated cellulose and microfibrillated dialdehyde cellulose and method for manufacturing the barrier film

    CN110506143A

  • A method for producing a film having good barrier properties and a film having good barrier properties

    CN111479858A

  • Gas barrier film for packaging material

    CN113382855A

  • Packaging coatings, packaging products, and methods of making

    US20220127486A1